toner

By using a resin combination with silicon group and azo group in the toner to form a hydrogen bond crosslinked structure, the problem of insufficient low-temperature fixation and high-temperature storage performance in the prior art is solved, and efficient low-temperature fixation and high-temperature storage effects are achieved.

JP7665311B2Active Publication Date: 2025-04-21CANON KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020178374
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-23
Publication Date
2025-04-21
Estimated Expiration
2040-10-23

AI Technical Summary

Technical Problem

The prior art is difficult to achieve the balance between low-temperature fixation and high-temperature storage at the same time, resulting in insufficient low-temperature fixation performance and poor thermal stability.

Method used

The -toner particles containing resin A and resin B with alternative or unsubstituted silicon group are used to form a strong crosslinked structure through hydrogen bonding between the silicon group and the azo group, which improves thermal stability and rapidly dissociate at high temperatures to reduce melt viscosity and improve low-temperature fixation performance.

Benefits of technology

High compatibility is achieved to improve the performance of low-temperature fixation and high-temperature storage, avoiding trade-off between thermal stability and low-temperature fixation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665311000001
    Figure 0007665311000001
  • Figure 0007665311000002
    Figure 0007665311000002
  • Figure 0007665311000003
    Figure 0007665311000003
Patent Text Reader

Abstract

To provide a toner that can strike a good balance between low temperature fixability and heat-resistant storage.SOLUTION: A toner contains a toner particle, where the toner particle contains a resin A and a resin B, the resin A has a substituted or unsubstituted silyl group in a molecule, and a substituent of the substituted silyl group is at least one selected from the group consisting of an alkyl group having one or more carbon atoms, an alkoxy group having one or more carbon atoms, a hydroxy group, a halogen atom, and an aryl group having 6 or more carbon atoms. The resin B has an azo group in a molecule.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a toner used to form a toner image by developing an electrostatic latent image formed by a method such as electrophotography, electrostatic recording, or toner jet recording. [Background technology]

[0002] In recent years, there has been a demand for printers and copiers with lower power consumption, and therefore a demand for improved low-temperature fixing properties of toners. At the same time, there is a demand for toners that can be used without problems in various environments, and therefore there is a demand for improved heat-resistant storage stability of toners. In order to satisfy both of these requirements, it is necessary to resolve the trade-off between softening the toner during fixing and suppressing changes in physical properties during storage at high temperatures. In order to eliminate this trade-off and achieve both low-temperature fixability and heat-resistant storage stability, various studies have been conducted. Patent Document 1 discloses a toner containing, as a binder resin, a vinyl resin obtained by copolymerizing a vinyl monomer with a silane coupling agent having an unsaturated double bond and an alkoxysilyl group in order to achieve both low-temperature fixing property and heat-resistant storage stability. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 7-239573 Summary of the Invention [Problem to be solved by the invention]

[0004] The method described in the above document is a method for improving the heat-resistant storage stability that has been conventionally desired, but there is still room for improvement in low-temperature fixability. Furthermore, in order to achieve the toner performance that will be required in the future, it is necessary to simultaneously satisfy two contradictory toner performance requirements, that is, to further improve low-temperature fixability while also greatly improving heat-resistant storage stability, but the methods described in the above documents are still insufficient. It is described that the crosslinking between alkoxysilyl groups in the toner (the formation of siloxane bonds) has the effect of preventing deformation of the toner through a three-dimensional network structure of the binder resin, thereby improving heat-resistant storage stability. However, it was found that the method described in the above document does not sufficiently reduce the melt viscosity of the toner even at high temperatures during fixing, and is not fully satisfactory in terms of low-temperature fixing properties. Conversely, if the crosslinking density between alkoxysilyl groups is reduced to sufficiently lower the melt viscosity of the toner in order to improve low-temperature fixability, the network structure of the binder resin will naturally decrease, causing the toner to melt easily even during storage, lowering the heat-resistant storage stability. Furthermore, even if the Tg of the binder resin is lowered as a method for improving low-temperature fixability while the crosslink density is increased in order to maintain the heat-resistant storage stability, the crosslinks do not undergo thermal decomposition and the melt viscosity of the toner is unlikely to decrease, so no significant improvement in low-temperature fixability could be confirmed.

[0005] As described above, the method described in the above document has been unable to resolve the trade-off between heat-resistant storage stability and low-temperature fixability despite various attempts, and it has been difficult to achieve a high degree of compatibility between low-temperature fixability and heat-resistant storage stability of a toner. The present disclosure provides a toner that can achieve both high levels of low-temperature fixability and high-temperature storage stability. [Means for solving the problem]

[0006] The present disclosure provides a toner comprising toner particles, The toner particles contain a binder resin, a resin A, and a resin B, The resin A has a substituted or unsubstituted silyl group in the molecule and has a structure represented by the following formula (1): TIFF0007665311000001.tif33170(In formula (1), P 1 represents the polyester resin portion, and L1 represents a single bond or a divalent linking group, R 1 ~R 3 each independently represents a hydrogen atom, a halogen atom, an alkyl group having one or more carbon atoms, an alkoxy group having one or more carbon atoms, an aryl group having six or more carbon atoms, or a hydroxy group; R 1 ~R 3 At least one of the groups represents an alkoxy group having one or more carbon atoms or a hydroxy group, m represents a positive integer, and when m is 2 or more, a plurality of L 1 , multiple R 1 , multiple R 2 and multiple R 3 may be the same or different.) the substituent of the substituted silyl group is at least one selected from the group consisting of an alkyl group having one or more carbon atoms, an alkoxy group having one or more carbon atoms, a hydroxy group, a halogen atom, and an aryl group having six or more carbon atoms; The toner has an azo group in the molecule. Effect of the Invention

[0007] The present disclosure makes it possible to provide a toner that can achieve both high levels of low-temperature fixability and high-temperature storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] In the present disclosure, the expressions "XX or more and YY or less" and "XX to YY" representing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified. When numerical ranges are stated in stages, the upper and lower limits of each numerical range can be combined in any way.

[0009] As a result of extensive research aimed at solving the problems of the conventional techniques described above, the present inventors have found that the following toner can achieve both low-temperature fixability and high-temperature storage stability at a high level. The present disclosure provides a toner comprising toner particles, The toner particles contain a binder resin, a resin A, and a resin B, The resin A has a substituted or unsubstituted silyl group in the molecule, the substituent of the substituted silyl group is at least one selected from the group consisting of an alkyl group having one or more carbon atoms, an alkoxy group having one or more carbon atoms, a hydroxy group, a halogen atom, and an aryl group having six or more carbon atoms; The toner has an azo group in the molecule.

[0010] The present inventors speculate as follows about the mechanism by which it is possible to achieve both low-temperature fixability and high-temperature storage stability at a higher level than conventional toners. When the toner is stored, inside the toner particles, the silyl groups in resin A form hydrogen bonds with the azo groups in resin B. This forms a strong cross-linked structure between resin A and resin B. Hydrogen bonds are formed between multiple molecules to form a network structure, making the toner less likely to deform and significantly improving heat-resistant storage stability.

[0011] On the other hand, the crosslinked structure due to the hydrogen bond is quickly dissociated in the high temperature region, which is the fixing temperature, and the above-mentioned network structure inside the entire toner particle is quickly dissolved. As a result, the melt viscosity of the toner is significantly reduced during fixing, and the low-temperature fixing property can be significantly improved. That is, it was found that the network structure does not collapse during storage of the toner, resulting in excellent heat resistance storage stability, and that the hydrogen bonds are quickly broken during fixing, resulting in the network structure being dissolved, resulting in excellent low-temperature fixing properties. The toner will now be described.

[0012] <Resin A> The toner particles contain a resin A. The toner particles preferably contain, in their interiors (cores), a resin A. Furthermore, the resin A is preferably an organic resin. Resin A (a) has a substituted or unsubstituted silyl group in the molecule, and (b) the substituent of the substituted silyl group is at least one selected from the group consisting of an alkyl group having one or more carbon atoms, an alkoxy group having one or more carbon atoms, a hydroxy group, a halogen atom, and an aryl group having six or more carbon atoms. The alkyl group preferably has 1 to 20 carbon atoms, more preferably 1 to 4 carbon atoms. do. The alkoxy group preferably has 1 to 20 carbon atoms, more preferably 1 to 4, further preferably 1 to 3, and particularly preferably 1 or 2 carbon atoms. The aryl group preferably has 6 to 14 carbon atoms, and more preferably 6 to 10 carbon atoms. Preferred examples of the resin A are not limited as long as they satisfy the above (a) and (b), and include polymers of organic resins and organosilicon compounds chemically bonded with silane coupling agents, etc., and hybrid resins thereof, etc. More specifically, resins obtained by modifying polyester resins, vinyl resins, polycarbonate resins, polyurethane resins, phenol resins, epoxy resins, polyolefin resins, or styrene-acrylic resins with silane coupling agents and / or silicone oils, etc., are included.

[0013] Resin A preferably has a structure represented by the following formula (1): This allows hydrogen bonds to be efficiently formed between Resin A and Resin B.

[0014] [ka]

[0015] (In the formula (1), P 1 represents the polymer moiety, and L 1 represents a single bond or a divalent linking group, R 1 ~R 3 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 or more carbon atoms, an alkoxy group having 1 or more carbon atoms, an aryl group having 6 or more carbon atoms, or a hydroxyl group; m represents a positive integer; and when m is 2 or more, 1 , multiple R 1 , multiple R 2 and multiple R 3 may be the same or different.)

[0016] R in the above formula (1) 1 ~R 3 At least one of the R in formula (1) is preferably an alkoxy group having one or more carbon atoms or a hydroxy group. 1 ~R 3 each independently represents an alkoxy group having 1 or more carbon atoms or a hydroxy group. Of the above substituents, the number of carbon atoms in the alkyl group is preferably 1 to 20, more preferably 1 to 4. The number of carbon atoms in the alkoxy group is preferably 1 to 20, more preferably 1 to 4, even more preferably 1 to 3, and particularly preferably 1 or 2. The number of carbon atoms in the aryl group is preferably 6 to 14, more preferably 6 to 10.

[0017] The content of silicon atoms in Resin A is preferably 0.02% by mass to 10.00% by mass. By setting the content in this range, the amount of hydrogen bonds with the azo groups in Resin B can be more appropriately adjusted, so that both heat-resistant storage stability and low-temperature fixability can be more highly achieved. The content of silicon atoms in Resin A is more preferably from 0.10% by mass to 5.00% by mass, and even more preferably from 0.20% by mass to 5.00% by mass. The silicon atom content in Resin A can be controlled by adjusting the amount of silicon compound used in producing Resin A. The content of resin A in the toner particles is preferably 0.1% by mass to 90.0% by mass, more preferably 0.3% by mass to 30.0% by mass, even more preferably 1.0% by mass to 10.0% by mass, and still more preferably 1.5% by mass to 5.0% by mass. More preferred.

[0018] R in the above formula (1) 1 ~R 3 When at least one of these represents an alkoxy group or a hydroxy group having one or more carbon atoms, the structure represented by the formula (1) has a Si-O- bond. Since the Si-O bond easily forms a hydrogen bond with the azo group in resin B, a network structure is formed by hydrogen bonds between resin A and resin B that efficiently spreads throughout the entire interior of the toner, greatly improving heat-resistant storage stability.

[0019] R in the above formula (1) 1 ~R 3 In order to make one or more of R into a hydroxy group, 1 ~R 3 Resin A in which one or more of the above groups are alkoxy groups may be hydrolyzed to convert the alkoxy groups into hydroxy groups. The hydrolysis may be carried out by any method, for example, the following method. R in the above formula (1) 1 ~R 3 Resin A, in which one or more of the above groups are alkoxy groups, is dissolved or suspended in a suitable solvent (which may be a polymerizable monomer), and the pH is adjusted to acidic using an acid or alkali, followed by mixing and hydrolysis. Further, hydrolysis may occur during the production of toner particles.

[0020] P in the above formula (1) 1 Examples of the resin moiety include, but are not limited to, a polyester resin moiety, a vinyl resin moiety, a styrene acrylic resin moiety, a polyurethane resin moiety, a polycarbonate resin moiety, a phenolic resin moiety, a polyolefin resin moiety, and the like. Among these, from the viewpoint of achieving both heat resistance and low temperature fixability, P 1 It is preferable that P contains a styrene acrylic resin moiety or a polyester resin moiety. 1 may be a hybrid resin moiety of polyester resin and styrene-acrylic resin. 1 is more preferably a styrene acrylic resin moiety.

[0021] The reason for this is believed to be as follows: The styrene acrylic resin portion or polyester resin portion has few intermolecular interactions and is likely to form a network structure of resin A and resin B that are spread out in the binder resin, which contributes to stabilizing the shape of the entire toner particle and improves heat-resistant storage stability. In addition, by forming a network with a large area, the hydrogen bond sites formed by the silyl groups in Resin A and the azo groups in Resin B tend to be uniformly dispersed in the toner particles. This increases the thermal response and greatly improves low-temperature fixing properties. In particular, P 1 If the styrene acrylic resin is used, P 1 Since the charge stability of the toner in a high temperature and high humidity environment is higher than that in the case where the polyester resin portion is used, the toner is more suitable for use in a wider range of environments, which is preferable.

[0022] The reason for this is believed to be as follows. Hydrogen bonds are formed between the silyl group in resin A and the azo group in resin B, and at this time, the azo group becomes δ- and the silyl group becomes δ+, resulting in polarization. The negative charge generated on the toner surface is transferred to the P 1 As the charge propagates, it diffuses into the toner. P 1 When the charge propagates through the 1 Depending on the insulating properties of the material itself, it may affect the charging stability of the toner. 1 If the insulating property of is extremely low, the negative charge will be transferred quickly to P via the silyl group. 1 Since the toner is diffused into the toner particles, the charge of the toner may decay and sufficient charge stability may not be expected. P 1 By increasing the insulating property to a certain degree, it becomes possible to suppress excessive charge decay, and therefore the charging stability can be improved. In particular, P 1 If it is a styrene acrylic resin moiety, P 1 Since the insulating property is higher than that of polyester resin, it was found that the charging stability is high even in high temperature and high humidity environments. .

[0023] The styrene-acrylic resin and vinyl resin are not particularly limited and may be any known resin. For example, the following monomers may be used. Styrenic monomers such as styrene and its derivatives, such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-methoxystyrene, p-phenylstyrene, p-chlorostyrene, 3,4-dichlorostyrene, p-ethylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, and pn-dodecylstyrene. Acrylic acid esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, propyl acrylate, n-octyl acrylate, dodecyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, 2-chloroethyl acrylate, and phenyl acrylate. Methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, dodecyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, phenyl methacrylate, dimethylaminoethyl methacrylate, and diethylaminoethyl methacrylate.

[0024] Amino group-containing α-methylene aliphatic monocarboxylic acid esters such as dimethylaminoethyl methacrylate and diethylaminoethyl methacrylate; vinyl monomers containing nitrogen atoms such as acrylic acid or methacrylic acid derivatives such as acrylonitrile, methacrylonitrile, and acrylamide. Vinyl monomers containing a carboxy group, such as unsaturated dibasic acids, such as maleic acid, citraconic acid, itaconic acid, alkenylsuccinic acid, fumaric acid, and mesaconic acid; α,β-unsaturated acids, such as acrylic acid, methacrylic acid, crotonic acid, and cinnamic acid; and acid anhydrides thereof.

[0025] L as a linking group 1 In order to form the above, the styrene-acrylic resin or vinyl resin may contain a carboxy group. The method for incorporating a carboxy group into a styrene-acrylic resin or vinyl resin is not particularly limited, and any known method can be used. For example, it is preferable to use a vinyl monomer containing a carboxy group, such as acrylic acid or methacrylic acid. The styrene-acrylic resin in the styrene-acrylic resin portion is preferably a polymer of at least one selected from the group consisting of acrylic acid esters and methacrylic acid esters, a styrene-based monomer, and a vinyl-based monomer containing a carboxy group.

[0026] The styrene-acrylic resin portion is preferably a copolymer of a styrene-based monomer and a (meth)acrylic acid ester. In the styrene-acrylic resin portion, the ratio of the styrene-based monomer can be set in the range of 0.0 mol % to 100.0 mol %, and is preferably in the range of 50.0 mol % to 85.0 mol %.

[0027] The polyester resin is not particularly limited, but is preferably a condensate of a dialcohol and a dicarboxylic acid. For example, a polyester resin having a structure represented by the following formula (6) and at least one structure (multiple structures can be selected) selected from the group consisting of structures represented by the following formulas (7) to (9) is preferred. Alternatively, a polyester resin having a structure represented by the following formula (10) is also preferred.

[0028] [ka]

[0029] (In formula (6), R 9 represents an alkylene group, an alkenylene group, or an arylene group. 10 represents an alkylene group or a phenylene group. 18 represents an ethylene group or a propylene group. x and y are each an integer of 0 or more, and the average value of x+y is 2 to 10. In formula (10), R 11 represents an alkylene group or an alkenylene group.

[0030] R in the above formula (6) 9 Examples of the alkylene group (preferably having 1 to 12 carbon atoms) in the above formula include the following: a methylene group, an ethylene group, a trimethylene group, a propylene group, a tetramethylene group, a hexamethylene group, a neopentylene group, a heptamethylene group, an octamethylene group, a nonamethylene group, a decamethylene group, an undecamethylene group, a dodecamethylene group, 1,3-cyclopentylene, 1,3-cyclohexylene, and 1,4-cyclohexylene group. R in the above formula (6) 9 Examples of the alkenylene group (preferably having 2 to 4 carbon atoms) in the formula include a vinylene group, a propenylene group, and a 2-butenylene group. R in the above formula (6) 9 Examples of the arylene group (preferably having 6 to 12 carbon atoms) in the formula include a 1,4-phenylene group, a 1,3-phenylene group, a 1,2-phenylene group, a 2,6-naphthylene group, a 2,7-naphthylene group, and a 4,4'-biphenylene group. R in the above formula (6) 9 may be substituted with a substituent, in which case, examples of the substituent include a methyl group, a halogen atom, a carboxy group, a trifluoromethyl group, and combinations thereof.

[0031] R in the above formula (7) 10 As the alkylene group (preferably having 1 to 12 carbon atoms) in Examples of the alkyl group include the following: a methylene group, an ethylene group, a trimethylene group, a propylene group, a tetramethylene group, a hexamethylene group, a neopentylene group, a heptamethylene group, an octamethylene group, a nonamethylene group, a decamethylene group, an undecamethylene group, a dodecamethylene group, 1,3-cyclopentylene, 1,3-cyclohexylene, and 1,4-cyclohexylene group. R in the above formula (7) 10 Examples of the phenylene group in include a 1,4-phenylene group, a 1,3-phenylene group, and a 1,2-phenylene group. R in the above formula (7) 10may be substituted with a substituent, in which case, examples of the substituent include a methyl group, an alkoxy group, a hydroxy group, a halogen atom, and combinations thereof.

[0032] R in the above formula (10) 11 Examples of the alkylene group (preferably having 1 to 12 carbon atoms) in the above formula include the following: a methylene group, an ethylene group, a trimethylene group, a propylene group, a tetramethylene group, a hexamethylene group, a neopentylene group, a heptamethylene group, an octamethylene group, a nonamethylene group, a decamethylene group, an undecamethylene group, a dodecamethylene group, and a 1,4-cyclohexylene group. R in the above formula (10) 11 In the above, examples of the alkenylene group (preferably having 2 to 40 carbon atoms) include the following: vinylene group, propenylene group, butenylene group, butadienylene group, pentenylene group, hexenylene group, hexadienylene group, heptenylene group, octanylene group, decenylene group, octadecenylene group, eicosenylene group, and triacontenylene group. These alkenylene groups may have any of a linear, branched, and cyclic structure. The position of the double bond may be any position, as long as there is at least one double bond. R in the above formula (10) 11 may be substituted with a substituent. In this case, the substituent that may be substituted includes an alkyl group, an alkoxy group, a hydroxy group, a halogen atom, and combinations thereof.

[0033] L in the above formula (1) 1 Examples of the divalent linking group that can be represented include structures represented by the following formulas (2) to (5), but are not particularly limited thereto.

[0034] [ka]

[0035] (R in Equation (2) 5represents a single bond, an alkylene group, or an arylene group. (*) represents a group represented by the formula (1 ) in P 1 represents the bonding site to the silicon atom in formula (1) above, and (**) represents the bonding site to the silicon atom in formula (1) above. R in Equation (3) 6 represents a single bond, an alkylene group, or an arylene group. (*) represents P in formula (1). 1 represents the bonding site to the silicon atom in formula (1) above, and (**) represents the bonding site to the silicon atom in formula (1) above. R in formulas (4) and (5) 7 and R 8 Each of the groups independently represents an alkylene group, an arylene group, or an oxyalkylene group. 1 (**) represents the bonding site to the silicon atom in formula (1).

[0036] Among these, L 1 is preferably a divalent linking group containing an amide bond represented by the above formula (2) in terms of improving the brittleness of the toner. It is presumed that the reason for the improvement in brittleness is that the amide bond in formula (2) and the azo group in resin B exhibit dipole-dipole interactions. When the brittleness of the toner is improved, even if the toner is subjected to stress due to contact with parts during the development process, problems such as cracking or chipping of the toner do not occur, contamination of parts is reduced, and a stable development process can be realized.

[0037] The structure represented by the formula (2) is a divalent linking group containing an amide bond. The linking group can be formed, for example, by reaction of a carboxy group in the resin with an aminosilane. The aminosilane is not particularly limited, but examples thereof include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, N-phenylγ-aminopropyltriethoxysilane, N-phenylγ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, N-6-(aminohexyl)3-aminopropyltrimethoxysilane, 3-aminopropyltrimethylsilane, and 3-aminopropylsilane. R 5 The alkylene group (preferably having 1 to 12 carbon atoms, more preferably 2 to 4 carbon atoms) in is not particularly limited, and may be, for example, an alkylene group containing an --NH-- group. R 5 The arylene group (preferably having 6 to 12 carbon atoms, more preferably 6 to 10 carbon atoms) in the formula (I) is not particularly limited, and may be, for example, an arylene group containing a hetero atom.

[0038] The structure represented by the formula (3) is a divalent linking group containing a urethane bond. The linking group can be formed, for example, by reaction of a hydroxy group in the resin with an isocyanate silane. The isocyanate silane is not particularly limited, but examples thereof include 3-isocyanate propyl trimethoxy silane, 3-isocyanate propyl methyl dimethoxy silane, 3-isocyanate propyl dimethyl methoxy silane, 3-isocyanate propyl triethoxy silane, 3-isocyanate propyl methyl diethoxy silane, and 3-isocyanate propyl dimethyl ethoxy silane. R 6 The alkylene group (preferably having 1 to 12 carbon atoms, more preferably 2 to 4 carbon atoms) in is not particularly limited, and may be, for example, an alkylene group containing an --NH-- group. R 6The arylene group (preferably having 6 to 12 carbon atoms, more preferably 6 to 10 carbon atoms) in the formula (I) is not particularly limited, and may be, for example, an arylene group containing a hetero atom.

[0039] The structure represented by the formula (4) or (5) is a divalent linking group containing a bond grafted to an ester bond in the resin. The linking group is formed, for example, by an insertion reaction of an epoxysilane. The insertion reaction of epoxysilane refers to a reaction that includes a process of inserting an epoxy group of epoxysilane into an ester bond contained in the main chain of a resin. The insertion reaction referred to here refers to, for example, a reaction described as "insertion reaction of an epoxy compound into an ester bond in a polymer chain" in Organic Synthesis Chemistry, Vol. 49, No. 3, p. 218, 1991. The reaction mechanism of the epoxysilane insertion reaction can be represented by the following model diagram.

[0040] [ka]

[0041] (In the figure, D and E indicate the resin components, and F indicates the epoxy compound component.) In the diagram, the ring-opening of the epoxy group can involve α-cleavage or β-cleavage, resulting in two types of compounds. In either case, the epoxy group is inserted into the ester bond in the resin; in other words, the components of the epoxy compound other than the epoxy moiety are grafted to the resin. The epoxy silane is not particularly limited, but examples thereof include β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and the like.

[0042] R 7 and R 8The alkylene group (preferably having 1 to 12 carbon atoms, more preferably 2 to 4 carbon atoms) in is not particularly limited, and may be, for example, an alkylene group containing an --NH-- group. R 7 and R 8 The arylene group (preferably having 6 to 12 carbon atoms, more preferably 6 to 10 carbon atoms) in the formula (I) is not particularly limited, and may be, for example, an arylene group containing a hetero atom. R 7 and R 8 The oxyalkylene group (preferably having 1 to 12 carbon atoms, more preferably 2 to 4 carbon atoms) in the formula (I) is not particularly limited, and may be, for example, an oxyalkylene group containing an --NH-- group.

[0043] The weight average molecular weight (Mw) of resin A is preferably from 2,000 to 100,000, more preferably from 3,000 to 100,000, and even more preferably from 8,000 to 35,000, from the viewpoint of achieving both heat-resistant storage stability and low-temperature fixability. Resin A is preferably a polymer in order to further improve heat-resistant storage stability. The weight-average molecular weight (Mw) of resin A is preferably 2000 or more. When in the above range, resin A and the azo groups in resin B form hydrogen bonds, which makes it easy to form a three-dimensionally expanding network, thereby further improving heat-resistant storage stability. From the viewpoint of improving low-temperature fixability, the weight average molecular weight (Mw) of the resin A is preferably 100,000 or less.

[0044] The Mw of the resin A can be controlled by various methods depending on the type of resin contained. For example, when a polyester resin is contained, it can be controlled by adjusting the ratio of the monomers dialcohol and dicarboxylic acid, or by adjusting the polymerization time. When a styrene-acrylic resin is contained, it can be controlled by adjusting the ratio of the monomer vinyl monomer and polymerization initiator, or by adjusting the reaction temperature.

[0045] <Resin B> The toner particles contain a resin B. The resin B is a resin having an azo group in the molecule. Specifically, the resin having an azo group is a resin in which a "compound containing an azo group" is linked to an "organic resin." The "compound containing an azo group" in resin B may be an aliphatic azo compound, an aromatic azo compound, a β-diketone azo compound, or the like. Any type of azo compound is preferably used because it forms a hydrogen bond with the silyl group in resin A.

[0046] Among them, the compound containing an azo group is more preferably an aromatic azo compound represented by the following formula (11) or a β-diketone azo compound represented by the following formula (12). Ar 1 -N=N-Ar 2 (11) In formula (11), Ar 1 , Ar 2 Each of Ar independently represents a substituted or unsubstituted aromatic group. Examples of the substituent include an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a hydroxyl group, a halogen atom, and combinations thereof. 1 , Ar 2 At least one of the groups has a substituent that forms a bonding site with the organic resin in Resin B as a “linking group”.

[0047] Ar 1 , Ar 2 Each of Ar is preferably a substituted or unsubstituted aryl group (preferably having 6 to 12 carbon atoms, more preferably having 6 to 10 carbon atoms). 1 , Ar 2 Examples of the substituent that may be included in the resin B include an amino group, a hydroxy group, a carboxy group, a methyl group, a dimethylamino group, an aminocarbonyl group, an aminocarbonylamino group, an alkyloxycarbonyl group having 1 to 4 carbon atoms, an imidazolidinone structure, or a combination thereof. Examples of the substituent that may be included in the resin B as a linking group and that forms a bonding site with the organic resin in the resin B include an amino group, a hydroxy group, or a carboxy group. For example, an amide bond can be formed with the organic resin in Resin B via an amino group or a carboxy group as a linking group. Also, for example, an ester bond with the organic resin in Resin B can be formed as a linking group by a hydroxy group or a carboxy group.

[0048] Ar 1 , Ar 2 More preferably, each independently represents a phenyl group, an aminophenyl group, a hydroxyphenyl group, a carboxyphenyl group, a methylphenyl group, or a dimethylaminophenyl group. 1 , Ar 2 At least one of the groups is preferably a hydroxyphenyl group, a carboxyphenyl group, or an aminophenyl group, and more preferably an aminophenyl group. The aminophenyl group can form an amide bond with the carboxy group of the organic resin in Resin B as a linking group.

[0049] Resin B can be obtained by reacting the compound of formula (11) with an organic resin to form, for example, an ester bond, an amide bond, or a urethane bond as a linking group. That is, Resin B preferably has a structure represented by the following formula (11A). Ar 11 -N=N-Ar 21 (11A) In formula (11A), Ar 11 , Ar 21 Each independently represents a substituted or unsubstituted aromatic group. 1 , Ar 2 The substituents of the alkyl group include an amino group, a hydroxy group, a carboxy group, a methyl group, a dimethylamino group, an aminocarbonyl group, an aminocarbonylamino group, a carbonyl group, and a methyl group. Examples of the alkyloxycarbonyl group include an alkyloxycarbonyl group having 1 to 4 carbon atoms, an imidazolidinone structure, and a combination thereof. 11 , Ar 21 At least one of these has a substituent, which serves as a “linking group” to form a bonding site with the organic resin in Resin B. More preferably, Ar 11 , Ar 21 each independently has a structure represented by the following formulas (A) to (F), 11 , Ar 21 At least one of the above has a structure represented by the following formula (A) or (B). In formula (A) or (B), *** represents a bonding site with resin B. In formula (B), X represents a single bond or an alkylene group having 1 to 6 carbon atoms. The structures represented by formulas (A) to (F) are substituted or unsubstituted, and examples of the substituent include an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a hydroxy group, a halogen atom, and combinations thereof.

[0050] [ka]

[0051] The β-diketone azo compound represented by formula (12) is as follows.

[0052] [ka]

[0053] In formula (12), R 5 , R 6 each independently represents a substituted or unsubstituted alkyl group, a substituted or unsubstituted phenyl group, OR 7 group, or NR 8 R 9 R 7 ~R 9 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted phenyl group, or an aralkyl group. Ar 3 R represents a substituted or unsubstituted aryl group. 5 , R 6 and Ar 3 The substituent in the above is an amino group, a hydroxy group, a carboxy group, a methyl group, a dimethylamino group, an aminocarbonyl group, an aminocarbonylamino group, an alkyloxycarbonyl group having 1 to 4 carbon atoms, or the like. Examples of the compound include an alkyl group, an imidazolidinone structure, or a combination thereof. However, R 5 , R 6 , and Ar 3 At least one of the groups has a substituent that forms a bonding site with the organic resin in Resin B as a “linking group”.

[0054] R 5 , R 6 each independently represents an alkyl group having 1 to 3 carbon atoms, or -NR 8 R 9 R is preferably a group. 5 , R 6 At least one of the groups is -NR 8 R 9 More preferably, R 8 is a hydrogen atom, and R 9 is preferably an aminophenyl group. The aminophenyl group can form, for example, an amide bond with a carboxy group of an organic resin in Resin B as a linking group. Ar 3 is preferably a group represented by the following formulas (I) to (IV). 21 ,R 22 are each independently an alkyl group having 1 to 4 carbon atoms. The structures represented by formulas (I) to (IV) are substituted or unsubstituted, and examples of the substituent include an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a hydroxy group, a halogen atom, and combinations thereof.

[0055] [ka]

[0056] Resin B can be obtained by reacting the compound of formula (12) with an organic resin to form, for example, an ester bond, an amide bond, or a urethane bond as a linking group. That is, Resin B preferably has a structure represented by the following formula (12A). In formula (12A), R 51 , R 61each independently represents a substituted or unsubstituted alkyl group, a substituted or unsubstituted phenyl group, OR 7 group, or NR 8 R 9 R 7 ~R 9 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted phenyl group, or an aralkyl group. Ar 31 R represents a substituted or unsubstituted aryl group. 51 , R 61 , Ar 31 Examples of the substituents of R include an amino group, a hydroxy group, a carboxy group, a methyl group, a dimethylamino group, an aminocarbonyl group, an aminocarbonylamino group, an alkyloxycarbonyl group having 1 to 4 carbon atoms, an imidazolidinone structure, or a combination thereof. 51 , R 61 , Ar 31 At least one of the groups has a substituent, which serves as a "linking group" to form a bonding site with the organic resin in resin B.

[0057] [ka]

[0058] R 51 , R 61 are each preferably independently an alkyl group having 1 to 3 carbon atoms or a structure represented by the following formula (X): 51 , R 61 It is more preferable that at least one of the above has a structure represented by the following formula (X): *** in formula (X) represents a bonding site with resin B. Ar 31 is preferably a group represented by the above formulas (I) to (IV). 21 ,R 22are each independently an alkyl group having 1 to 4 carbon atoms. The structures represented by formulae (I) to (IV) and (X) are substituted or unsubstituted, and examples of the substituent include an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a hydroxy group, a halogen atom, and combinations thereof.

[0059] [ka]

[0060] The linking group in the resin B is not particularly limited, and may be an amide group, an ester group, a urethane group, a urea group, an alkylene group, a phenylene group, a group represented by -O-, -NR 20 - (R 20 represents a hydrogen atom, an alkyl group, a phenyl group, or an aralkyl group.) and divalent linking groups having a partial structure represented by -NHCH(CHOH)-, etc. The linking group is preferably an amide group or an ester group.

[0061] R 20 Examples of the alkyl group in the formula (I) include linear, branched, or cyclic alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an n-butyl group, an n-pentyl group, an n-hexyl group, an isopropyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, and a cyclohexyl group. R 20 Examples of the aralkyl group in the formula (I) include a benzyl group and a phenethyl group.

[0062] The "organic resin" in Resin B is not particularly limited, but examples thereof include a polyester resin portion, a vinyl portion, a styrene acrylic resin portion, a polyurethane resin portion, a polycarbonate resin portion, a phenolic resin portion, and a polyolefin resin portion.

[0063] Among these, from the viewpoint of achieving both heat-resistant storage stability and low-temperature fixability, the "organic resin" preferably contains a styrene-acrylic resin moiety and / or a polyester resin moiety. The organic resin may also be, for example, a hybrid resin moiety of a polyester resin and a styrene-acrylic resin. The "organic resin" is more preferably a styrene-acrylic resin moiety or a polyester resin moiety. From the viewpoint of suppressing charge-up in a low-temperature, low-humidity environment, it is even more preferable that the organic resin is a styrene-acrylic resin moiety. The styrene-acrylic resin and polyester resin in the styrene-acrylic resin portion and polyester resin in the polyester resin portion are the same as those described above for resin A.

[0064] Furthermore, the content of resin B in the toner particles is preferably 0.1% by mass to 90.0% by mass, more preferably 0.3% by mass to 30.0% by mass, even more preferably 1.0% by mass to 10.0% by mass, and even more preferably 1.5% by mass to 5.0% by mass.

[0065] The weight average molecular weight (Mw) of Resin B is preferably from 2,000 to 100,000, more preferably from 3,000 to 100,000, and even more preferably from 10,000 to 30,000, from the viewpoint of achieving both heat-resistant storage stability and low-temperature fixability. From the viewpoint of improving heat-resistant storage stability, the weight average molecular weight (Mw) of Resin B is preferably equal to or greater than 2000. When the weight average molecular weight is within this range, a network that spreads three-dimensionally is easily formed. From the viewpoint of low-temperature fixability, the weight-average molecular weight (Mw) of Resin B is preferably 100,000 or less.

[0066] The Mw of the resin B can be controlled by various methods depending on the type of resin contained. For example, when a polyester resin is contained, it can be controlled by adjusting the ratio of the monomers dialcohol and dicarboxylic acid, or by adjusting the polymerization time. When a styrene-acrylic resin is contained, it can be controlled by adjusting the ratio of the monomer vinyl monomer and polymerization initiator, or by adjusting the reaction temperature.

[0067] <Binding resin> The toner particles contain a binder resin. When the glass transition temperature Tg of resin A in the toner particles is Tg(A), the Tg of resin B is Tg(B), and the Tg of the binder resin is Tg(C), it is preferable to satisfy the following relationship between (i) and (ii) from the viewpoint of achieving both heat-resistant storage stability and low-temperature fixability of the toner. Tg(A)>Tg(C) (i) Tg(B)>Tg(C) (ii)

[0068] In order to improve low-temperature fixing ability, the Tg(C) of the binder resin is lowered to reduce the heat melt viscosity of the toner, but this can cause the binder resin to become soft even during toner storage. It was discovered that the presence of a network formed by resin (A) and resin (B) is effective in providing resistance to deformation of toner particles caused by a soft binder resin. The network formed by resin (A) and resin (B) is thought to play a role similar to a skeleton inside the toner particles. In particular, satisfying the above conditions (i) and (ii) is effective in achieving both high-temperature storage stability and low-temperature fixability. Tg(A)-Tg(C) is preferably from 5°C to 50°C, and more preferably from 10°C to 45°C. Tg(B)-Tg(C) is preferably from 2°C to 25°C, and more preferably from 5°C to 20°C.

[0069] Tg(A) is preferably from 55°C to 100°C, and more preferably from 60°C to 95°C. Tg(B) is preferably 52°C to 75°C, more preferably 55°C to 70°C. This is more preferable. The Tg(C) is preferably from 40°C to 60°C, and more preferably from 45°C to 55°C.

[0070] In the toner particles, the content of resin A relative to 100.0 parts by mass of the binder resin is preferably 0.1 parts by mass to 20.0 parts by mass, more preferably 0.3 parts by mass to 5.0 parts by mass, and even more preferably 1.5 parts by mass to 4.5 parts by mass. In addition, the content of resin B in the toner particles relative to 100.0 parts by mass of the binder resin is preferably 0.1 parts by mass to 20.0 parts by mass, more preferably 0.3 parts by mass to 5.0 parts by mass, and even more preferably 1.5 parts by mass to 4.5 parts by mass.

[0071] The binder resin is not particularly limited, and any conventionally known binder resin can be used, but for example, vinyl resins, polyester resins, etc. are preferred. Examples of the vinyl resins, polyester resins, and other binder resins include the following resins or polymers. The vinyl resin is preferably a styrene-acrylic resin.

[0072] Homopolymers of styrene and its substituted derivatives, such as polystyrene and polyvinyltoluene; Styrenic copolymers such as styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-dimethylaminoethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-dimethylaminoethyl methacrylate copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; Polymethyl methacrylate, polybutyl methacrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resin, polyamide resin, epoxy resin, polyacrylic resin, rosin, modified rosin, terpene resin, phenol resin, aliphatic or alicyclic hydrocarbon resin, and aromatic petroleum resin. These binder resins may be used alone or in combination of two or more.

[0073] From the viewpoint of electrostatic chargeability, the binder resin preferably contains a carboxy group, and is preferably a resin produced using a polymerizable monomer containing a carboxy group. Specific examples of the polymerizable monomer containing a carboxy group include, but are not limited to, the following polymerizable monomers: (Meth)acrylic acids such as α-ethylacrylic acid and crotonic acid, and their α-alkyl or β-alkyl derivatives; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, itaconic acid, etc.; unsaturated dicarboxylic acid monoester derivatives such as succinic acid monoacryloyloxyethyl ester, succinic acid monoacryloyloxyethylene ester, phthalic acid monoacryloyloxyethyl ester, phthalic acid monomethacryloyloxyethyl ester, etc.

[0074] As the polyester resin, a resin obtained by polycondensation of a carboxylic acid component and an alcohol component as shown below can be used. Examples of the carboxylic acid component include terephthalic acid, isophthalic acid, phthalic acid, fumaric acid, maleic acid, cyclohexanedicarboxylic acid, and trimellitic acid. Examples of the alcohol component include bisphenol A, hydrogenated bisphenol, ethylene oxide adduct of bisphenol A, and propylene oxide adduct of bisphenol A. Additives include glycerin, trimethylolpropane, and pentaerythritol.

[0075] The polyester resin may be a polyester resin containing a urea group. It is preferable that the carboxyl group present at the terminal of the polyester resin is not capped. In order to improve the viscosity change of the toner at high temperatures, the binder resin may have a polymerizable functional group, such as a vinyl group, an isocyanate group, an epoxy group, an amino group, a carboxy group, or a hydroxy group.

[0076] In addition to the above, the same monomer as that in the styrene-acrylic resin portion of the resin A can also be used for the vinyl resin or styrene-acrylic resin in the binder resin. The binder resin is preferably a copolymer of styrene and an alkyl (meth)acrylate having an alkyl group with 1 to 8 carbon atoms (preferably 2 to 6 carbon atoms), more preferably a styrene-butyl acrylate copolymer. The copolymerization ratio (styrene:alkyl (meth)acrylate (mass ratio)) is preferably 55:45 to 80:20, more preferably 60:40 to 70:30.

[0077] <Crosslinking agent> In order to control the molecular weight of the binder resin, a crosslinking agent may be added during polymerization of the polymerizable monomer. As the crosslinking agent, for example, the following compounds can be used, but the crosslinking agent is not limited thereto. Ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol diacrylate, divinylbenzene, bis(4-acryloxypolyethoxyphenyl)propane, ethylene glycol diacrylate, 1,3-butylene glycol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol #200, #400, #600 diacrylates, dipropylene glycol diacrylate, polypropylene glycol diacrylate and polyester type diacrylate (MANDA Nippon Kayaku), as well as those in which the above acrylates have been replaced with methacrylates. The amount of the crosslinking agent added is preferably 0.001 to 15.0 parts by mass with respect to 100 parts by mass of the polymerizable monomer.

[0078] <Release agent> The toner particles may contain a wax. Examples of the wax that can be used include, but are not limited to, the following waxes: Monohydric alcohol and aliphatic monocarboxylic acid esters, such as behenyl behenate, stearyl stearate, and palmityl palmitate, or esters of monohydric carboxylic acids and aliphatic monoalcohols; dihydric alcohol and aliphatic monocarboxylic acid esters, such as dibehenyl sebacate and hexanediol dibehenate, or esters of dihydric carboxylic acids and aliphatic monoalcohols; trihydric alcohol and aliphatic monocarboxylic acid esters, such as glycerin tribehenate, or esters of trihydric carboxylic acids and aliphatic monoalcohols; tetrahydric alcohol and aliphatic monocarboxylic acid esters, such as pentaerythritol tetrastearate and pentaerythritol tetrapalmitate, or esters of tetrahydric carboxylic acids and aliphatic monoalcohols. esters of cholesteryl; esters of hexavalent alcohols and aliphatic monocarboxylic acids such as dipentaerythritol hexastearate and dipentaerythritol hexapalmitate, or esters of hexavalent carboxylic acids and aliphatic monoalcohols; esters of polyhydric alcohols and aliphatic monocarboxylic acids such as polyglycerin behenate, or esters of polyvalent carboxylic acids and aliphatic monoalcohols; natural ester waxes such as carnauba wax and rice wax; petroleum-based waxes and derivatives thereof such as paraffin wax, microcrystalline wax, and petrolatum; hydrocarbon waxes and derivatives thereof produced by the Fischer-Tropsch process; polyolefin waxes and derivatives thereof such as polyethylene wax and polypropylene wax; higher aliphatic alcohols; fatty acids such as stearic acid and palmitic acid; and acid amide waxes. The wax content in the toner particles is preferably 0.5% by mass to 20.0% by mass.

[0079] <Coloring agent> The toner particles may contain a colorant. The colorant is not particularly limited, and the following known colorants can be used. Examples of yellow pigments that can be used include condensed azo compounds such as yellow iron oxide, navel yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, and tartrazine lake, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include the following. CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168, 180. Examples of orange pigments include the following: Permanent Orange GTR, Pyrazolone Orange, Balkan Orange, Benzidine Orange G, Induthrene Brilliant Orange RK, Induthrene Brilliant Orange GK. Examples of red pigments include condensed azo compounds such as red iron oxide, permanent red 4R, lithol red, pyrazolone red, watching red calcium salt, lake red C, lake red D, brilliant carmine 6B, brilliant carmine 3B, eosin lake, rhodamine lake B, and alizarin lake, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include the following. CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, 254. Examples of blue pigments include copper phthalocyanine compounds and their derivatives such as alkali blue lake, Victoria blue lake, phthalocyanine blue, metal-free phthalocyanine blue, phthalocyanine blue partial chloride, fast sky blue, and indanthrene blue BG, anthraquinone compounds, and basic dye lake compounds. Specific examples include the following. CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, 66. Examples of purple pigments include Fast Violet B and Methyl Violet Lake. Examples of green pigments include Pigment Green B, Malachite Green Lake, and Final Yellow Green G. Examples of white pigments include zinc oxide, titanium oxide, antimony white, and zinc sulfide. Examples of black pigments include carbon black, aniline black, non-magnetic ferrite and magnetite, as well as pigments toned to black using the above-mentioned yellow, red and blue colorants. These colorants may be used alone or in combination of two or more. These colorants may also be used in the form of a solid solution. If necessary, the colorant may be surface-treated with a substance that does not inhibit polymerization. The content of the colorant in the toner particles is preferably 3.0% by mass to 15.0% by mass.

[0080] <Charge control agent> The toner particles may contain a charge control agent. There is no particular limitation on the charge control agent, and any known charge control agent may be used. In particular, a charge control agent that has a high charging speed and can stably maintain a constant charge amount is preferred. Furthermore, when the toner particles are produced by a direct polymerization method, a charge control agent that has low polymerization inhibition properties and is substantially free of solubilized matter in an aqueous medium is particularly preferred. As the charge control agent that controls the toner particles to have a negative charge, the following can be mentioned, for example. Organometallic compounds and chelating compounds include monoazo metal compounds, acetylacetone metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, oxycarboxylic acids and dicarboxylic acid-based metal compounds. Other examples include aromatic oxycarboxylic acids, aromatic mono- and polycarboxylic acids and their metal salts, anhydrides or esters, and phenol derivatives such as bisphenol. Further examples include urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarenes.

[0081] On the other hand, examples of charge control agents that control the toner particles to be positively charged include the following. Nigrosine and nigrosine modifications such as fatty acid metal salts; guanidine compounds; imidazole compounds; onium salts such as quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthosulfonate, tetrabutylammonium tetrafluoroborate, and their analogues such as phosphonium salts, and lake pigments thereof; triphenylmethane dyes and lake pigments thereof (lake agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide, ferrocyanide, etc.); metal salts of higher fatty acids; resin-based charge control agents. These charge control agents may be used alone or in combination of two or more. The content of these charge control agents in the toner particles is preferably 0.01% by mass to 10.0% by mass.

[0082] <External additives> The toner particles can be used without adding any external additives. However, in order to improve the flowability, chargeability, cleaning properties, etc., so-called external additives such as a fluidizing agent and a cleaning aid may be added to the toner. Examples of the external additive include inorganic oxide fine particles such as silica fine particles, alumina fine particles, and titanium oxide fine particles, inorganic stearic acid compound fine particles such as aluminum stearate fine particles and zinc stearate fine particles, and inorganic titanic acid compound fine particles such as strontium titanate and zinc titanate. These may be used alone or in combination of two or more. These inorganic particles are made of silane coupling agents, titanium coupling agents, higher fatty acids, silicone oils, etc., to improve heat resistance, storage stability, and environmental stability. It is preferable that the external additive is treated with a BET specific surface area of ​​10 m 2 / g~450m 2 It is preferred that the molecular weight is / g.

[0083] The BET specific surface area is determined by a low-temperature gas adsorption method using a dynamic constant pressure method in accordance with the BET method (preferably the BET multipoint method). For example, a specific surface area measuring device (product name: Gemini 2375 Ver. 5.0, manufactured by Shimadzu Corporation) is used to adsorb nitrogen gas onto the surface of a sample, and the BET multipoint method is used to measure the BET specific surface area (m 2 / g) is calculated. The total amount of these various external additives added is preferably 0.05 parts by mass to 10.00 parts by mass, more preferably 0.10 parts by mass to 5.00 parts by mass, based on 100.00 parts by mass of toner particles. Also, various external additives may be used in combination.

[0084] <Developer> The toner can be used as a magnetic or non-magnetic one-component developer, but may also be mixed with a carrier and used as a two-component developer. As the carrier, magnetic particles made of known materials such as metals such as iron, ferrite, magnetite, and alloys of these metals with metals such as aluminum and lead can be used. Of these, it is preferable to use ferrite particles. As the carrier, a coated carrier in which the surface of magnetic particles is coated with a coating agent such as resin, or a resin dispersion type carrier in which magnetic fine powder is dispersed in a binder resin can also be used. The carrier preferably has a volume average particle size of 15 μm to 100 μm, and more preferably 25 μm to 80 μm.

[0085] <About the manufacturing method of toner particles> The toner particles can be produced by known methods, such as a kneading and grinding method or a wet production method. From the viewpoint of uniform particle size and shape controllability, a wet production method is preferably used. Further, examples of the wet production method include a suspension polymerization method, a dissolution suspension method, an emulsion polymerization aggregation method, and an emulsion aggregation method.

[0086] Here, the suspension polymerization method will be described. The suspension polymerization method may include a step of preparing a polymerizable monomer composition by uniformly dissolving or dispersing a polymerizable monomer for producing a binder resin, resin A, resin B, and other additives such as a colorant as necessary, using a dispersing machine such as a ball mill or ultrasonic dispersing machine (a step of preparing a polymerizable monomer composition). At this time, a multifunctional monomer, a chain transfer agent, a wax as a release agent, a charge control agent, a plasticizer, and the like can be appropriately added as necessary. Suitable examples of the polymerizable monomer in the suspension polymerization method include the vinyl polymerizable monomers shown below.

[0087] Styrene; styrene derivatives such as α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, p-methoxystyrene, and p-phenylstyrene; methyl acrylate, ethyl acrylate, n-propyl acrylate, iso-propyl acrylate, n-butyl acrylate, and iso-butyl acrylate. acrylate polymerizable monomers such as tert-butyl acrylate, n-amyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-nonyl acrylate, cyclohexyl acrylate, benzyl acrylate, dimethyl phosphate ethyl acrylate, diethyl phosphate ethyl acrylate, dibutyl phosphate ethyl acrylate, and 2-benzoyloxyethyl acrylate; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, Methacrylic polymerizable monomers such as n-butyl methacrylate, iso-butyl methacrylate, tert-butyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, n-nonyl methacrylate, diethyl phosphate ethyl methacrylate, and dibutyl phosphate ethyl methacrylate; methylene aliphatic monocarboxylic acid esters; vinyl esters such as vinyl acetate, vinyl propionate, vinyl benzoate, vinyl butyrate, and vinyl formate; vinyl ethers such as vinyl methyl ether, vinyl ethyl ether, and vinyl isobutyl ether; vinyl methyl ketone, vinyl hexyl ketone, and vinyl isopropyl ketone.

[0088] The suspension polymerization method may include a step (granulation step) of adding the polymerizable monomer composition to a previously prepared aqueous medium and forming droplets of the polymerizable monomer composition into a desired toner particle size using a stirrer or disperser having high shear force. It is preferable that the aqueous medium in the granulation process contains a dispersion stabilizer in order to control the particle size of the toner particles, to sharpen the particle size distribution, and to suppress the coalescence of the toner particles during the manufacturing process. Dispersion stabilizers are generally broadly classified into polymers that exhibit repulsive force due to steric hindrance and poorly water-soluble inorganic compounds that stabilize dispersion by electrostatic repulsive force. Fine particles of poorly water-soluble inorganic compounds are preferably used because they dissolve in acid or alkali and can be easily removed by washing with acid or alkali after polymerization.

[0089] As the dispersion stabilizer of the poorly water-soluble inorganic compound, one containing any one of magnesium, calcium, barium, zinc, aluminum, and phosphorus is preferably used. More preferably, one containing any one of magnesium, calcium, aluminum, and phosphorus. Specific examples thereof include the following. Sodium phosphate, magnesium phosphate, tricalcium phosphate, aluminum phosphate, zinc phosphate, magnesium carbonate, calcium carbonate, magnesium hydroxide, calcium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, calcium chloride, hydroxyapatide. The above dispersion stabilizers may be used in combination with organic compounds such as polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch. The dispersion stabilizer is preferably used in an amount of 0.01 to 2.00 parts by mass with respect to 100.00 parts by mass of the polymerizable monomer.

[0090] Furthermore, in order to make these dispersion stabilizers finer, 0.001 to 0.100 parts by mass of a surfactant may be used in combination with 100.000 parts by mass of the polymerizable monomer. Specifically, commercially available nonionic surfactants, commercially available anionic surfactants, and commercially available cationic surfactants can be used. For example, sodium dodecyl sulfate, sodium tetradecyl sulfate, sodium pentadecyl sulfate, sodium octyl sulfate, sodium oleate, sodium laurate, potassium stearate, calcium oleate, etc. are preferably used.

[0091] The suspension polymerization method may include a step (polymerization step) of obtaining a toner base particle dispersion by polymerizing the polymerizable monomer contained in the polymerizable monomer composition at a temperature of preferably 50° C. to 90° C. The polymerization step may be performed after the granulation step or may be performed during the granulation step. In the polymerization step, it is preferable to carry out a stirring operation so that the temperature distribution in the vessel is uniform. When a polymerization initiator is added, it can be added at any timing and for any required time. In addition, the temperature may be raised in the latter half of the polymerization reaction in order to obtain a desired molecular weight distribution, and further, in order to remove unreacted polymerizable monomers, by-products, etc. from the system, a part of the aqueous medium may be distilled off by a distillation operation in the latter half of the reaction or after the reaction is completed. The distillation operation can be carried out under normal pressure or reduced pressure.

[0092] In the suspension polymerization method, an oil-soluble initiator is generally used. Examples of the initiator include the following: azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile; peroxide initiators such as acetylcyclohexylsulfonyl peroxide, diisopropyl peroxycarbonate, decanonyl peroxide, lauroyl peroxide, stearoyl peroxide, propionyl peroxide, acetyl peroxide, tert-butyl peroxy-2-ethylhexanoate, benzoyl peroxide, tert-butyl peroxyisobutyrate, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicumyl peroxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, tert-butyl peroxypivalate, and cumene hydroperoxide.

[0093] The polymerization initiator may be used in combination with a water-soluble initiator as necessary, and examples thereof include the following. Ammonium persulfate, potassium persulfate, 2,2'-azobis(N,N'-dimethyleneisobutyromidine) hydrochloride, 2,2'-azobis(2-aminodinopropane) hydrochloride, azobis(isobutylamidine) hydrochloride, 2,2'-azobisisobutyronitrile sodium sulfonate, ferrous sulfate, or hydrogen peroxide. These polymerization initiators can be used alone or in combination of two or more. In order to control the degree of polymerization of the polymerizable monomer, it is also possible to further use a chain transfer agent, a polymerization inhibitor, etc. in combination.

[0094] The measurement methods for each physical property value are described below. <Method for extracting resin A and resin B from toner> Resin A and Resin B are extracted from the toner by separating the extract using tetrahydrofuran (THF) by a solvent gradient elution method. The preparation method is shown below. Weigh out 10.0 g of toner particles, place them in a cylindrical filter paper (Toyo Roshi No. 84) and place them in a Soxhlet extractor. Extract for 20 hours using 200 mL of THF as the solvent, and the solid obtained by removing the solvent from the extract is the THF-soluble fraction. The THF-soluble fraction contains resin A and resin B. This is repeated several times to obtain the required amount of THF-soluble fraction. For the solvent gradient elution method, a gradient preparative HPLC (Shimadzu LC-20AP high pressure gradient preparative system, Waters SunFire preparative column 50 mm φ 250 mm) is used. The column temperature is 30°C, the flow rate is 50 mL / min, and the mobile phase uses acetonitrile as a poor solvent and THF as a good solvent. 0.02 g of the THF-soluble fraction obtained by extraction was dissolved in 1.5 mL of THF to prepare the sample for separation. The mobile phase started with a composition of 100% acetonitrile, and 5 minutes after the sample was injected, the ratio of THF was increased by 4% per minute until the mobile phase composition became 100% THF over 25 minutes. The components could be separated by drying the obtained fraction. This allows resin A and resin B to be isolated separately. Which fraction is resin A or resin B can be determined by measuring the silicon atom content and 13 It can be distinguished by C-NMR measurement.

[0095] <Method for measuring the content of silicon atoms in resin A> The silicon content in resin A is measured using a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical) and the accompanying dedicated software "SuperQ ver.4.0F" (PANalytical) for setting measurement conditions and analyzing measurement data. Rh is used as the anode of the X-ray tube, the measurement atmosphere is vacuum, the measurement diameter (collimator mask diameter) is 27 mm, and the measurement time is 10 seconds. In addition, a proportional counter (PC) is used to measure light elements, and a scintillation counter (SC) is used to measure heavy elements.

[0096] Binder particles [Product name: Spectro Blend, Ingredients: C81.0% by mass, O2.9% by mass, H13.5% by mass, N2.6% by mass, Chemical formula: C 19 H 38 SiO2 particles (hydrophobic fumed silica) [product name: AEROSIL NAX50, specific surface area: 40±10 m2] per 100.0 parts by mass of SiO2 particles (hydrophobic fumed silica) [product name: AEROSIL NAX50, specific surface area: 40±10 m2] 2 0.5 parts by mass of SiO2 particles (carbon content: 0.45% to 0.85%; manufactured by Nippon Aerosil Co., Ltd.) was added and thoroughly mixed using a coffee mill. Similarly, 5.0 parts by mass and 10.0 parts by mass of the SiO2 particles were mixed with the binder particles, respectively, to prepare samples for the calibration curve. For each sample, a pellet of the calibration curve sample is prepared as described above using a tablet press, and the count rate (unit: cps) of the Si-Kα ray observed at a diffraction angle (2θ) = 109.08° when PET is used as the analyzing crystal is measured. In this case, the acceleration voltage and current value of the X-ray generator are 24 kV and 100 mA, respectively. A linear function calibration curve is obtained by plotting the obtained X-ray count rate on the vertical axis and the amount of SiO2 particles added in each calibration curve sample on the horizontal axis.

[0097] The measurement sample was prepared by placing 4 g of resin A in a special aluminum ring for pressing, flattening it, and pressing it at 20 MPa for 60 seconds using a tablet molding compression machine "BRE-32" (manufactured by Maekawa Test Machinery Manufacturing Co., Ltd.) to form a pellet with a thickness of 2 mm and a diameter of 39 mm. The count rate of the Si-Kα radiation of the pellet is measured, and the content of silicon atoms in Resin A is calculated from the above calibration curve.

[0098] <Method for analyzing copolymer composition ratio of resin A and resin B> The structures of Resin A and Resin B are determined using the following apparatus. 1 H NMR: JEOL Ltd. ECA-400 (solvent: deuterated chloroform) 13C NMR: Bruker Biospin FT-NMR AVANCE-600 (solvent: deuterated chloroform) In addition, 13 C NMR was quantified and compositional analysis was performed using the inverse gated decoupling method with chromium(III) acetylacetonate as a relaxation reagent.

[0099] <Identification of the structures of Resin A and Resin B> The structure of resin A and resin B, for example, the polymer moiety P in the structure represented by formula (1) 1 , L 1 Part, R 1 ~R 3 The parts, etc. 1 H-NMR analysis, 13 C-NMR analysis, 29 The substance is identified using Si-NMR analysis and FT-IR analysis. L 1 When the compound contains an amide bond as represented by the formula (2), 1 It can be identified by H-NMR analysis. Specifically, it can be identified by the chemical shift value of the proton at the NH site of the amide group, and the amount of the amide group can be quantified by calculating the integral value. In addition, R in the structure represented by formula (1) 1 ~R 3 When contains an alkoxy group or a hydroxy group, 29 It is possible to determine the valence of an alkoxy group or a hydroxy group relative to a silicon atom by Si-NMR.

[0100] <Method of measuring weight average molecular weight (Mw)> The weight average molecular weight (Mw) of a resin is measured by gel permeation chromatography (GPC) as follows. First, the sample is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The resulting solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is prepared so that the concentration of components soluble in THF is 0.8 mass%. This sample solution is used to perform measurements under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: Shodex KF-801, 802, 803, 804, 805, 806, 80 7 of 7 (manufactured by Showa Denko) Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Oven temperature: 40.0℃ Sample injection volume: 0.1 mL In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (product names: "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation) is used.

[0101] <Method for measuring the acid value Av of resin> The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. The acid value of a resin is measured in accordance with JIS K 0070-1992, and specifically, it is measured according to the following procedure. (1) Preparation of reagents Dissolve 1 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), and add ion-exchanged water to make 100 mL to obtain a phenolphthalein solution. Dissolve 7 g of special grade potassium hydroxide in 5 mL of water and add ethyl alcohol (95% by volume) to make 1 L. Place in an alkali-resistant container to avoid contact with carbon dioxide, etc., leave for 3 days, then filter to obtain potassium hydroxide solution. Store the resulting potassium hydroxide solution in an alkali-resistant container. The factor of the potassium hydroxide solution is calculated by taking 25 mL of 0.1 mol / L hydrochloric acid in an Erlenmeyer flask, adding a few drops of the phenolphthalein solution, titrating with the potassium hydroxide solution, and calculating the amount of the potassium hydroxide solution required for neutralization. The 0.1 mol / L hydrochloric acid used is prepared in accordance with JIS K 8001-1998. (2) Operation (A) Main Test Weigh out 2.0 g of the crushed sample into a 200 ml Erlenmeyer flask, add 100 ml of a toluene / ethanol (2:1) mixed solution, and dissolve for 5 hours. Next, add a few drops of the phenolphthalein solution as an indicator, and titrate with the potassium hydroxide solution. The end point of the titration is when the light red color of the indicator continues for about 30 seconds. (B) Blank test The titration is carried out in the same manner as above, except that no sample is used (i.e., only the toluene / ethanol (2:1) mixed solution is used). (3) The obtained result is substituted into the following formula to calculate the acid value. A = [(CB) × f × 5.61] / S Here, A is the acid value (mgKOH / g), B is the amount of potassium hydroxide solution added for the blank test (ml), C is the amount of potassium hydroxide solution added for the main test (ml), f is the factor of the potassium hydroxide solution, and S is the mass of the sample (g).

[0102] <Method for measuring the hydroxyl value (OHv) of resin> The hydroxyl value is the amount of potassium hydroxide (mg) required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of a sample is acetylated. The hydroxyl value of a resin is measured according to JIS K 0070-1992, and more specifically, it is measured according to the following procedure. (1) Preparation of reagents Put 25 g of special grade acetic anhydride into a 100 mL measuring flask, add pyridine to make the total volume 100 mL, and shake thoroughly to obtain the acetylation reagent. Store the obtained acetylation reagent in a brown bottle to avoid contact with moisture, carbon dioxide, etc. Dissolve 1.0 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), and add ion-exchanged water to make 100 mL to obtain a phenolphthalein solution. Dissolve 35 g of special grade potassium hydroxide in 20 mL of water and add ethyl alcohol (95% by volume) to make 1 L. Place in an alkali-resistant container to avoid contact with carbon dioxide, etc., leave for 3 days, then filter to obtain potassium hydroxide solution. Store the resulting potassium hydroxide solution in an alkali-resistant container. The factor of the potassium hydroxide solution is calculated by placing 25 mL of 0.5 mol / L hydrochloric acid in an Erlenmeyer flask, adding a few drops of the phenolphthalein solution, titrating with potassium hydroxide solution, and calculating the amount of potassium hydroxide solution required for neutralization. 0.5 mol / L hydrochloric acid prepared in accordance with JIS K 8001-1998 is used. (2) Operation (A) Main Test Weigh out 1.0 g of the ground sample into a 200 mL round-bottom flask, and add 5.0 mL of the acetylation reagent accurately using a volumetric pipette. If the sample is difficult to dissolve in the acetylation reagent, add a small amount of special grade toluene to dissolve it. Place a small funnel on the mouth of the flask and immerse about 1 cm of the bottom of the flask in a glycerin bath at about 97°C and heat it. At this time, it is preferable to cover the base of the neck of the flask with a piece of cardboard with a round hole in it to prevent the temperature of the neck of the flask from rising due to the heat of the bath. After 1 hour, remove the flask from the glycerin bath and allow it to cool. After cooling, add 1 mL of water through the funnel and shake to hydrolyze the acetic anhydride. To further complete the hydrolysis, heat the flask again in the glycerin bath for 10 minutes. After cooling, wash the funnel and the walls of the flask with 5 mL of ethyl alcohol. Add a few drops of the phenolphthalein solution as an indicator and titrate with the potassium hydroxide solution. The end point of the titration is when the light red color of the indicator continues for about 30 seconds. (B) Blank test The titration is carried out in the same manner as above, except that no sample is used. (3) The obtained result is substituted into the following formula to calculate the hydroxyl value. A = [((B - C) × 28.05 × f) / S] + D Here, A: hydroxyl value (mgKOH / g), B: addition amount of potassium hydroxide solution in blank test (mL), C: addition amount of potassium hydroxide solution in this test (mL), f: factor of potassium hydroxide solution, S: mass of sample (g), D: acid value of sample (mgKOH / g).

[0103] <Method for Measuring Tg> The glass transition temperature (Tg) of resin A, resin B or the binder resin is measured in accordance with ASTM D3418 - 82 using a differential scanning calorimeter "Q2000" (manufactured by TA Instruments). As the measurement sample, about 2 mg of precisely weighed resin A, resin B or the binder resin is used. This is placed in an aluminum pan, and an empty aluminum pan is used as a reference. The measurement temperature range is set from 30°C to 200°C. Once the temperature is raised from 30°C to 200°C at a heating rate of 10°C / min, then the temperature is lowered from 200°C to 30°C at a cooling rate of 10°C / min, and then the temperature is raised to 200°C again at a heating rate of 10°C / min. In the DSC curve obtained in the second heating process, the intersection of the line at the midpoint between the baseline before and after the specific heat change occurs and the differential thermal curve is defined as the glass transition temperature Tg.

Examples

[0104] Hereinafter, the present invention will be specifically described with examples, but the present invention is not limited to these examples. Unless otherwise specified, all "parts" of each material in the examples and comparative examples are based on mass.

[0105] <Synthesis of Styrene - Acrylic Resin (R - 1)> The styrene - acrylic resin (R - 1) was synthesized as follows. 100.0 parts of propylene glycol monomethyl ether was heated while replacing with nitrogen, and refluxed at a liquid temperature of 120° C. or higher. A mixture of 80.2 parts of styrene, 20.1 parts of butyl acrylate, 5.0 parts of acrylic acid, and 1.0 part of tert-butyl peroxybenzoate [organic peroxide polymerization initiator, manufactured by NOF Corporation, product name: Perbutyl Z] was added dropwise thereto over 3 hours. After the dropwise addition was completed, the solution was stirred for 3 hours, and then distilled at normal pressure while increasing the liquid temperature to 170° C. After the liquid temperature reached 170° C., the pressure was reduced to 1 hPa, and distillation was performed for 1 hour to remove the solvent, obtaining a resin solid. The resin solid was dissolved in tetrahydrofuran, reprecipitated with n-hexane, and the precipitated solid was filtered to obtain a styrene-acrylic resin (R-1). The resulting styrene-acrylic resin (R-1) had an acid value of 36.6 mg KOH / g and Mw=22,000.

[0106] <Synthesis of styrene acrylic resin (R-2)> A styrene-acrylic resin (R-2) was synthesized as follows. 100.0 parts of propylene glycol monomethyl ether was heated while replacing with nitrogen, and refluxed at a liquid temperature of 120° C. or higher. A mixture of 72.9 parts of styrene, 21.6 parts of acrylic acid, and 1.0 part of tert-butyl peroxybenzoate [organic peroxide polymerization initiator, manufactured by NOF Corporation, product name: Perbutyl Z] was added dropwise thereto over 3 hours. After the dropwise addition was completed, the solution was stirred for 3 hours, and then distilled at normal pressure while increasing the liquid temperature to 170° C. After the liquid temperature reached 170° C., the pressure was reduced to 1 hPa, and distillation was performed for 1 hour to remove the solvent, obtaining a resin solid. The resin solid was dissolved in tetrahydrofuran, reprecipitated with n-hexane, and the precipitated solid was filtered to obtain a styrene-acrylic resin (R-2). The resulting styrene-acrylic resin (R-2) had an acid value of 154.6 mg KOH / g and Mw=22,000.

[0107] <Synthesis of acrylic resin (R-3)> An acrylic resin (R-3) was synthesized as follows. 100.0 parts of propylene glycol monomethyl ether was heated while replacing with nitrogen, and refluxed at a liquid temperature of 120° C. or higher. A mixture of 30.0 parts of methyl methacrylate, 50.4 parts of acrylic acid, and 1.0 part of tert-butyl peroxybenzoate [organic peroxide polymerization initiator, manufactured by NOF Corporation, product name: Perbutyl Z] was added dropwise thereto over 3 hours. After the dropwise addition was completed, the solution was stirred for 3 hours, and then distilled at normal pressure while increasing the liquid temperature to 170° C. After the liquid temperature reached 170° C., the pressure was reduced to 1 hPa, and distillation was performed for 1 hour to remove the solvent, obtaining a resin solid. The resin solid was dissolved in tetrahydrofuran, reprecipitated with n-hexane, and the precipitated solid was filtered off to obtain an acrylic resin (R-3). The resulting acrylic resin (R-3) had an acid value of 351.8 mg KOH / g and Mw=8,700.

[0108] <Synthesis of polyester (R-4)> Polyester (R-4) was synthesized according to the following procedure. The following materials were charged into an autoclave equipped with a pressure reducing device, a water separating device, a nitrogen gas introducing device, a temperature measuring device, and a stirrer, and a reaction was carried out under a nitrogen atmosphere at normal pressure and 200°C for 5 hours. Bisphenol A-propylene oxide 2.1 mole adduct: 39.6 parts Terephthalic acid: 8.0 parts Isophthalic acid: 7.6 parts Tetrabutoxytitanate: 0.1 parts Then, 0.01 parts of trimellitic acid and 0.12 parts of tetrabutoxytitanate were added, and the mixture was reacted at 220°C for 3 hours, and then reacted under reduced pressure of 10 mmHg to 20 mmHg for 2 hours. Thus, polyester (R-4) was obtained. The resulting polyester (R-4) had an acid value of 6.1 mgKOH / g, a hydroxyl value of 33.6 mgKOH / g, and Mw=10,200.

[0109] <Synthesis of polyester (R-5)> Polyester (R-5) was synthesized according to the following procedure. The following materials were charged into an autoclave equipped with a pressure reducing device, a water separating device, a nitrogen gas introducing device, a temperature measuring device, and a stirrer, and a reaction was carried out under a nitrogen atmosphere at normal pressure and 200°C for 5 hours. Bisphenol A-propylene oxide 2 mole adduct: 21.0 parts Ethylene glycol: 2.1 parts Isosorbide: 0.6 parts Terephthalic acid: 14.8 parts Tetrabutoxytitanate: 0.1 parts Thereafter, 1.1 parts of trimellitic acid and 0.1 parts of tetrabutoxytitanate were added, and the mixture was reacted at 220° C. for 3 hours, and then reacted under reduced pressure of 10 mmHg to 20 mmHg for 2 hours to obtain polyester (R-5). The resulting polyester (R-5) had an acid value of 6.0 mg KOH / g, a hydroxyl value of 32.4 mg KOH / g, and Mw=10,400.

[0110] <Synthesis of polyester (R-6)> Polylactic acid [(polyester (R-6)] was synthesized according to the following procedure. The following materials were charged into an autoclave equipped with a pressure reducing device, a water separating device, a nitrogen gas introducing device, a temperature measuring device, and a stirrer, and a reaction was carried out under a nitrogen atmosphere at normal pressure and 200°C for 5 hours. Lactic acid: 100.0 parts Tetrabutoxytitanate: 0.1 parts Then, 0.1 parts of tetrabutoxy titanate was added, and the mixture was reacted at 220°C for 3 hours, and then reacted under reduced pressure of 10 mmHg to 20 mmHg for 2 hours. The obtained resin was dissolved in chloroform, and the solution was dropped into ethanol for reprecipitation and filtration to obtain polyester (R-6). The resulting polyester (R-6) had an acid value of 3.5 mgKOH / g and Mw=30,000.

[0111] <Synthesis of polyester (R-7)> Polyester (R-7) was obtained in the same manner as in the synthesis of polyester (R-4), except that 39.6 parts of bisphenol A-propylene oxide 2.1 mol adduct was changed to 33.2 parts of bisphenol A-ethylene oxide 2 mol adduct. The resulting polyester (R-7) had an acid value of 5.8 mg KOH / g, a hydroxyl value of 34.3 mg KOH / g, and Mw=10,800.

[0112] <Synthesis of polyester (R-8)> Poly(ε-caprolactone) having a stearyl ester at the carboxylic acid terminal [(polyester (A-8)]] was synthesized by the following procedure. The following materials were charged into a reaction vessel equipped with a nitrogen gas inlet device, a temperature measuring device, and a stirrer, and the reaction was carried out at 100° C. for 5 hours under a nitrogen atmosphere. Stearyl alcohol: 3.0 parts ε-caprolactone: 38.2 parts Titanium(IV) tetraisopropoxide: 0.5 parts The resin obtained was dissolved in chloroform, and the solution was dropped into methanol to reprecipitate the resin, followed by filtration. By filtering the mixture, a polyester (R-8) was obtained. The resulting polyester (R-8) had an acid value of 0.0 mgKOH / g, a hydroxyl value of 30.3 mgKOH / g, and Mw=8,300.

[0113] <Synthesis of polyesters (R-9) and (R-10)> Polyesters (R-9) and (R-10) were synthesized in the same manner as in the synthesis of polyester (R-4), except that the reaction pressure, reaction temperature and reaction time were adjusted so as to obtain the desired molecular weight. The physical properties of the resulting polyesters (R-9) and (R-10) are shown in Table 1.

[0114] <Production Example of Resin A> <Production Example of Resin (A-1)> Resin (A-1) represented by formula (1) was produced according to the following procedure. 50.0 parts of styrene acrylic resin (R-1) was dissolved in 200.0 parts of N,N-dimethylacetamide, 7.1 parts of 3-aminopropyltriethoxysilane as a silane compound, and 9.8 parts of DMT-MM [4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride] as a condensation agent were added, and the mixture was stirred at room temperature for 5 hours. After the reaction was completed, the solution was dropped into methanol, reprecipitated, and filtered to obtain resin (A-1). The physical properties of the obtained resin are shown in Table 2.

[0115] <Production Examples of Resins (A-2) to (A-6) and (A-10) to (A-16)> Resins (A-2) to (A-6) and (A-10) to (A-16) were obtained in the same manner as in the production example of resin (A-1), except that the type of base raw resin, the type and amount of modified silane compound, and the amount of DMT-MM added were changed as shown in Table 1. The physical properties of these obtained resins are shown in Table 2.

[0116] <Production Example of Resin (A-9)> Resin (A-4) 10.0 parts was dissolved in toluene 90.0 parts, mixed with pure water 400.0 parts, and stirred, and the pH was adjusted to 4.0 with dilute hydrochloric acid, and stirred at room temperature for 10.8 hours, and then the stirring was stopped and the mixture was transferred to a separatory funnel to extract the oil phase. The oil phase was concentrated and reprecipitated with methanol to obtain resin (A-9) represented by formula (1). The obtained resin (A-9) 29 When analyzed by Si-NMR measurement, R in formula (1) 1 ~R 3 were all hydroxy groups.

[0117] <Production Example of Resin (A-7)> Resin A (A-7) was synthesized in which a linking group represented by formula (4) or formula (5) was formed by an insertion reaction of an epoxy group in an epoxysilane with an ester bond in a polyester (R-7). 50.0 parts of polyester (R-7) was dissolved in 100.0 parts of anisole, 12.2 parts of (3-glycidoxypropyl)trimethoxysilane, and 10.0 parts of tetrabutylphosphonium bromide were added, and the mixture was heated and stirred at about 140°C for 5 hours under a nitrogen atmosphere. After cooling, the reaction mixture was dissolved in 200 ml of chloroform, dropped into methanol, reprecipitated, and filtered to obtain resin A (A-7). The physical properties of the obtained resin are shown in Table 2.

[0118] <Production example of resin (A-8)> Resin A (A-8) was synthesized as follows, in which a hydroxy group in polyester (R-8) was reacted with an isocyanate group in isocyanate silane to form a urethane bond. 50.0 parts of polyester (R-8) was dissolved in 500.0 parts of chloroform, and 6.6 parts of 3-isocyanatepropyltriethoxysilane and 0.5 parts of titanium (IV) tetraisopropoxide were added under a nitrogen atmosphere, followed by stirring at room temperature for 5 hours. After the reaction was completed, the solution was The resin was then reprecipitated and filtered to obtain Resin A (A-8). The physical properties of the resin obtained are shown in Table 2.

[0119] <Production example of resin (A-17)> Diphenylmethane diisocyanate (MDI) 41.3 parts Bisphenol A ethylene oxide 2 mole adduct (BPA-2EO) 33.8 parts Tetrahydrofuran (THF) 300.0 parts The above was charged into a reaction vessel equipped with a stirrer and a thermometer while replacing with nitrogen. After heating to 50°C and carrying out a urethane reaction for 8 hours, 1.0 part of 3-isocyanatepropyltriethoxysilane was added and the reaction was carried out for another 8 hours, and 3.0 parts of t-butyl alcohol were added to modify the isocyanate terminal. The solvent THF was distilled off to obtain resin (A-17).

[0120] [Table 1]

[0121] [Table 2] *1: Silicon atom content in resin A (mass%)

[0122] <Production example of resin B> <Synthesis Example of Compound (16) Containing an Azo Group> According to the following scheme, compound (16) containing an azo group was obtained.

[0123] [ka]

[0124] First, 3.1 parts of 4-nitroaniline (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to 30.0 parts of chloroform, and the mixture was cooled to below 10°C on ice, and 1.9 parts of diketene (manufactured by Tokyo Chemical Industry Co., Ltd.) was added. Then, the mixture was stirred at 65.0°C for 2 hours. After the reaction was completed, the mixture was extracted with chloroform and concentrated to obtain the compound of formula (14). Next, 40.0 parts of methanol and 5.3 parts of concentrated hydrochloric acid were added to 4.3 parts of diethyl 2-aminoterephthalate (Merck Ltd.), and the mixture was ice-cooled to below 10° C. To this solution, a solution of 2.1 parts of sodium nitrite in 6.0 parts of water was added, and the mixture was reacted at the same temperature for 1 hour. Next, 1.0 part of sulfamic acid was added and stirred for another 20 minutes (diazonium salt solution). 4.5 parts of the compound of formula (14) was added to 70.0 parts of methanol and cooled to below 10°C with ice. The diazonium salt solution was added. Then, a solution of 5.8 parts of sodium acetate in 7.0 parts of water was added, and the mixture was reacted at 10° C. or less for 2 hours. After the reaction was completed, 300 parts of water was added and the mixture was stirred for 30 minutes, and the solid was filtered off and purified by recrystallization from N,N-dimethylformamide to obtain the compound of formula (15). Next, 8.6 parts of compound (15) and 0.4 parts of palladium-activated carbon (palladium 5%) were added to 150.0 parts of N,N-dimethylformamide, and the mixture was stirred for 3 hours at 40° C. under a hydrogen gas atmosphere (reaction pressure: 0.1 to 0.4 MPa). After the reaction was completed, the solution was filtered and concentrated to obtain compound (16) containing an azo group.

[0125] <Synthesis Example of Compound (17) Containing an Azo Group> In the synthesis example of the azo group-containing compound (16), 4.3 parts of diethyl 2-aminoterephthalate (Merck Ltd.) was used, but 2.8 parts of 3-aminobenzamide (Tokyo Chemical Industry Co., Ltd.) was used instead. Except for this, the synthesis was carried out in the same manner as in the synthesis example of the azo group-containing compound (16), to obtain the azo group-containing compound (17).

[0126] [ka]

[0127] <Synthesis Example of Compound (18) Containing an Azo Group> In the synthesis example of the azo group-containing compound (16), 4.3 parts of diethyl 2-aminoterephthalate (Merck Ltd.) was used, but 3.1 parts of 5-amino-2-benzimidazolinone (Tokyo Chemical Industry Co., Ltd.) was used instead. Except for this, the synthesis was carried out in the same manner as in the synthesis example of the azo group-containing compound (16), to obtain the azo group-containing compound (18).

[0128] [ka]

[0129] <Synthesis Example of Compound (19) Containing an Azo Group> In the synthesis example of the azo group-containing compound (16), 4.3 parts of diethyl 2-aminoterephthalate (Merck Ltd.) was used, but 3.1 parts of (3-aminophenyl)urea (Waterstone Technology, LLC) was used. Except for this, the synthesis example of the azo group-containing compound (16) was performed in the same manner as in the synthesis example of the azo group-containing compound (16), to obtain the azo group-containing compound (19).

[0130] [ka]

[0131] <Production Example of Resin (B-1)> Resin (B-1) was produced according to the following procedure.

[0132] [ka]

[0133] 50.0 parts of styrene acrylic resin (R-1) was dissolved as an "organic resin" in 200.0 parts of N,N-dimethylacetamide, 14.1 parts of formula (16) as an "azo group-containing compound" and 9.8 parts of DMT-MM [4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride] as a condensing agent were added, and the mixture was stirred at room temperature for 5 hours. After the reaction was completed, the solution was dropped into methanol, reprecipitated, and filtered to obtain a resin (B-1) in which the "linking group" is an amide bond (-CONH-). The physical properties of the obtained resin are shown in Table 3.

[0134] <Production Examples of Resins (B-2) to (B-6) and (B-8) to (B-12)> Resins (B-2) to (B-6) and (B-8) to (B-12) were obtained in the same manner as in the production example of resin (B-1), except that the type of organic resin, the type and amount of compound containing an azo group, and the amount of DMT-MM added were changed as shown in Table 3 below. The physical properties of the obtained resins are shown in Table 3. In addition, formulas (20) to (21) in Table 3 represent compounds of the following formulas.

[0135] [ka]

[0136] <Production example of resin (B-7)> In 200.0 parts of N,N-dimethylacetamide, 50.0 parts of styrene acrylic resin (R-1) was dissolved as an "organic resin", 9.3 parts of formula (22) as an "azo group-containing compound", 9.8 parts of DMT-MM [4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride] as a condensing agent, and 3.9 parts of NMM (N-methylmorpholine) were added, and the mixture was stirred at room temperature for 5 hours. After the reaction was completed, the solution was dropped into methanol, reprecipitated, and filtered to obtain a resin (B-7) in which the "linking group" is an ester bond (-COO-). The physical properties of the obtained resin are shown in Table 3.

[0137] [ka]

[0138] [Table 3]

[0139] <Production Example of Toner Particle 1> Toner particles 1 were produced by the suspension polymerization method as follows. (Production of aqueous medium 1) A reaction vessel was charged with 390.0 parts of ion-exchanged water and 14.0 parts of sodium phosphate (12-hydrate) (manufactured by Rasa Kogyo Co., Ltd.), and the mixture was kept at 65° C. for 1.0 hour while purging with nitrogen. A calcium chloride aqueous solution in which 9.2 parts of calcium chloride (dihydrate) was dissolved in 10.0 parts of ion-exchanged water was added all at once while stirring at 12,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to prepare an aqueous medium containing a dispersion stabilizer. Further, 10% hydrochloric acid was added to the aqueous medium to adjust the pH to 6.0, thereby obtaining aqueous medium 1.

[0140] (Production of Polymerizable Monomer Composition 1) Styrene 65.0 parts Colorant (CI Pigment Blue 15:3) 6.5 parts The above material was placed in an attritor (manufactured by Nippon Coke & Engineering Co., Ltd.), and then zirconia particles having a diameter of 1.7 mm were added and dispersed at 220 rpm for 5.0 hours. After that, the zirconia particles were removed to prepare Dispersion 1 in which the colorant was dispersed. To the dispersion 1, the following materials were added: 35.0 parts n-butyl acrylate Resin (A-1) 3.0 parts ·Resin (B-1) 3.0 parts Polyester resin (R-4) 5.0 parts Fischer-Tropsch wax (melting point: 78°C) 7.0 parts The mixture was kept at 65° C. and uniformly dissolved and dispersed using a TK homomixer at 500 rpm to prepare a polymerizable monomer composition 1.

[0141] (granulation process) While keeping the temperature of aqueous medium 1 at 70°C and the rotation speed of the agitator at 12,000 rpm, Polymerizable monomer composition 1 was charged into system medium 1, and 9.0 parts of t-butyl peroxypivalate as a polymerization initiator was added thereto. Granulation was continued for 10 minutes while maintaining the stirring speed at 12,000 rpm by the stirring device.

[0142] (Polymerization process) The high-speed stirring device was changed to a stirrer equipped with a propeller stirring blade, and polymerization was carried out for 5.0 hours while stirring at 150 rpm and maintaining the temperature at 70°C. The polymerization reaction was then carried out by further heating to 85°C for 2.0 hours, thereby obtaining toner base particle dispersion liquid 1.

[0143] (Washing and filtration process) Thereafter, the pH was adjusted to 1.5 with 1 mol / L hydrochloric acid, and the mixture was stirred for 1 hour, and then filtered while being washed with ion-exchanged water. The obtained filter cake was dried in a dryer at 45° C. for 48 hours and sieved through a 75 μm mesh to obtain toner particles 1.

[0144] <Production Examples of Toner Particles 2 to 12> Toner particles 2 to 12 were obtained in the same manner as in the production example of toner particles 1, except that resin (B-1) was changed to resins (B-2) to (B-12), respectively.

[0145] <Production Examples of Toner Particles 13 to 28> Toner particles 13 to 28 were obtained in the same manner as in the production example of toner particles 1, except that resin (A-1) was changed to resins (A-2) to (A-17), respectively.

[0146] <Production Example of Toner Particles 32> Toner particles 32 were obtained in the same manner as in "Preparation of polymerizable monomer composition 1" in the preparation example of toner particles 1, except that 65.0 parts of styrene were changed to 94.0 parts, and 35.0 parts of n-butyl acrylate were changed to 6.0 parts.

[0147] <Production Example of Toner Particle 29> Toner particles 29 were produced by the kneading and pulverizing method as follows. The following materials were charged into an autoclave, and the atmosphere in the system was replaced with nitrogen. The temperature was then raised and maintained at 180°C with stirring. Low density polyethylene (melting point 100°C) 20.0 parts Styrene 64.0 parts n-Butyl acrylate 13.5 parts Acrylonitrile 2.5 parts Next, 50.0 parts of a 2.0 mass % xylene solution of t-butyl hydroperoxide was continuously added dropwise to the system over 4.5 hours, and after cooling, the solvent was separated and removed to obtain a graft polymer in which a styrene-acrylic copolymer was grafted to polyethylene.

[0148] Styrene / butyl acrylate copolymer 100.0 parts (Copolymer mass ratio: 70 mol / 30 mol, Mw=100,000, Tg=50°C) Resin (A-1) 3.0 parts ·Resin (B-1) 3.0 parts Paraffin wax (melting point: 75°C) 5.0 parts Graft polymer 5.0 parts CI Pigment Blue 15:3 5.0 parts The above materials were thoroughly mixed in an FM mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.), and then melt-kneaded in a twin-screw kneader (PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) set at a temperature of 100°C. The obtained kneaded product was cooled and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. Next, the resulting coarsely crushed material was finely ground using a Turbo Mill (T-250: RSS rotor / SNB liner) manufactured by Turbo Kogyo Co., Ltd. Thereafter, a multi-division classifier utilizing the Coanda effect was used to separate fine and coarse powders, thereby obtaining toner particles 29.

[0149] <Production Example of Toner Particles 30> Toner particles 30 were produced by the solution suspension method as follows. 660.0 parts of ion-exchanged water and 25.0 parts of a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate were mixed and stirred at 10,000 rpm using a TK homomixer to prepare an aqueous medium 2. The following materials were added to 500.0 parts of ethyl acetate and dissolved at 100 rpm with a propeller stirrer to prepare a solution. Styrene / butyl acrylate copolymer 100.0 parts (Copolymerization mass ratio: 70 / 30, Mw=100,000, Tg=50℃) Resin (A-1) 3.0 parts ·Resin (B-1) 3.0 parts Polyester (R-4) 5.0 parts Colorant (CI Pigment Blue 15:3) 6.5 parts Fischer-Tropsch wax (melting point: 78°C) 9.0 parts 150.0 parts of the aqueous medium 2 was placed in a vessel and stirred at 12,000 rpm using a TK homomixer, and 100.0 parts of the above-mentioned solution was added thereto and mixed for 10 minutes to prepare an emulsified slurry. Thereafter, 100.0 parts of the emulsified slurry was placed in a flask equipped with a degassing pipe, a stirrer, and a thermometer, and the solvent was removed under reduced pressure at 30° C. for 12 hours with stirring at 500 rpm, and then aged at 45° C. for 4 hours to obtain a solvent-free slurry. The solvent-removed slurry was filtered under reduced pressure, and then 300.0 parts of ion-exchanged water was added to the resulting filter cake, which was then mixed and redispersed in a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes), and then filtered. The obtained filter cake was dried in a dryer at 45° C. for 48 hours, and sieved through a mesh with an opening of 75 μm to obtain toner particles 30.

[0150] <Production Example of Toner Particles 31> Toner particles 31 were produced by the emulsion aggregation method as follows. (Production of Resin Particle Dispersion) The following materials were weighed, mixed and dissolved: Styrene 65.0 parts 35.0 parts n-butyl acrylate Acrylic acid 1.3 parts Resin (A-1) 3.0 parts ·Resin (B-1) 3.0 parts Hexanediol diacrylate 0.4 parts n-Lauryl mercaptan 3.2 parts A 10% aqueous solution of NEOGEN RK (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was added to the obtained solution and dispersed. An aqueous solution of 0.15 parts of potassium persulfate dissolved in 10.0 parts of ion-exchanged water was added while slowly stirring for another 10 minutes. After nitrogen replacement, emulsion polymerization was carried out at a temperature of 70°C for 6.0 hours. After polymerization was completed, the reaction solution was cooled to room temperature, and ion-exchanged water was added to obtain a resin particle dispersion with a solid content concentration of 12.5% ​​and a volume-based median diameter of 0.2 μm.

[0151] (Production of Wax Particle Dispersion) The following materials were weighed and mixed: Ester wax (melting point: 70°C) 100.0 parts Neogen RK (Daiichi Kogyo Seiyaku Co., Ltd.) 15.0 parts Ion-exchanged water 385.0 parts The material was dispersed for 1 hour using a wet jet mill JN100 (manufactured by Jokou Co., Ltd.) to obtain a wax particle dispersion liquid. The wax solids concentration in the wax particle dispersion liquid was 20.0%.

[0152] (Production of Colorant Particle Dispersion) The following materials were weighed and mixed: Colorant (CI Pigment Blue 15:3) 100.0 parts Neogen RK (Daiichi Kogyo Seiyaku Co., Ltd.) 15.0 parts Ion-exchanged water 885.0 parts The above materials were dispersed for 1 hour using a wet jet mill JN100 (manufactured by Jokou Co., Ltd.) to obtain a colorant particle dispersion liquid.

[0153] ·Resin particle dispersion liquid 160.0 parts Wax particle dispersion 10.0 parts Colorant particle dispersion 10.0 parts Magnesium sulfate 0.2 parts The above materials were dispersed using a homogenizer (IKA Ultra Turrax T50), and then heated to 65° C. while stirring. The mixture was stirred for 1.0 hour. 2.2 parts of NEOGEN RK (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was added thereto, and the mixture was heated to 80° C. and stirred for 2.0 hours to obtain fused spherical toner base particles. After cooling, the mixture was filtered, and the filtered solid was washed with 720.0 parts of ion-exchanged water by stirring for 1.0 hour. The solution containing the toner particles was filtered and dried using a vacuum dryer, toner particles 31 were obtained.

[0154] <Production Example of Comparative Toner Particle 1> On the assumption of the technology described in Patent Document 1, the Tg of the binder resin was lowered in order to further improve low-temperature fixability. Specifically, comparative toner particles 1 were obtained in the same manner as in the production example of toner particles 1, except that the resin (B-1) was not added.

[0155] <Production Example of Comparative Toner Particle 2> Comparative toner particles 2 were obtained in the same manner as in the production example of toner particles 1, except that the resin (A-1) was not added.

[0156] <Production Example of Comparative Toner Particle 3> In order to verify the case where resin B is not a "resin having an azo group" but a "low molecular weight compound having an azo group," comparative toner particles 3 were obtained in the same manner as in the production example of toner particles 1, except that resin (B-1) was changed to the compound represented by formula (20).

[0157] <Production Example of Comparative Toner Particle 4> In order to verify the case where resin A is not a "resin having a silyl group" but a "low molecular weight compound having a silyl group," comparative toner particles 4 were obtained in the same manner as in the production example of toner particles 1 described above, except that resin (A-1) was changed to "3-aminopropyltriethoxysilane."

[0158] <Production Example of Comparative Toner Particle 5> In order to verify the case where the resin A does not contain a silyl group, in the above-mentioned production example of toner particle 1, Comparative toner particles 5 were obtained in the same manner, except that the resin (A-1) was changed to a styrene acrylic resin (R-1).

[0159] <Toner 1 Manufacturing Example> 100 parts of toner particles 1 and a BET value of 200m 2 / g and 0.6 parts of hydrophobic silica fine particles having a number average particle size of primary particles of 8 nm were mixed in a Henschel mixer (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain toner 1.

[0160] <Production Examples of Toners 2 to 32 and Comparative Toners 1 to 5> Toners 2 to 32 and comparative toners 1 to 5 were obtained in the same manner as in the production example of toner 1, except that toner particles 1 were changed to toner particles 2 to 32 and comparative toner particles 1 to 5.

[0161] [Examples 1 to 32, Comparative Examples 1 to 5] The methods for evaluating the toners 1 to 32 and the comparative toners 1 to 5 are described below. 22、 The evaluation was performed as a reference example for No. 26 and No. 28 to No. 32. The evaluation results are shown in Table 4.

[0162] [Heat-resistant storage stability] 5.0 g of the toner was placed in a 100 ml resin cup and left to stand for 10 days at a temperature of 50° C. and a humidity of 10% RH. The degree of cohesion of the toner was then measured as follows and evaluated according to the following criteria. The measuring device used was a "Powder Tester" (manufactured by Hosokawa Micron Corporation) with a digital display vibration meter "DigiVibro MODEL 1332A" (manufactured by Showa Sokki Co., Ltd.) connected to the side of the vibration table. A sieve with a mesh size of 38 μm (400 mesh), a sieve with a mesh size of 75 μm (200 mesh), and a sieve with a mesh size of 150 μm (100 mesh) were placed on top of each other on the vibration table of the powder tester from the bottom up. The measurements were carried out in an environment of 23°C and 60% RH as follows. (1) The vibration amplitude of the vibration table was adjusted in advance so that the displacement value on the digital display vibrometer was 0.60 mm (peak-to-peak). (2) 5 g of the toner that had been left standing was precisely weighed and gently placed on the top sieve having 150 μm openings. (3) After the sieves were vibrated for 15 seconds, the mass of the toner remaining on each sieve was measured and the degree of cohesion was calculated according to the following formula. Coagulation degree (%) = {(mass (g) of sample on a sieve with 150 μm openings) / 5 (g)} x 100 + {(mass (g) of sample on a sieve with 75 μm openings) / 5 (g)} x 100 x 0.6 + {(Sample mass (g) on ​​38 μm mesh sieve) / 5(g)} x 100 x 0.2 The evaluation criteria are as follows. A: Coagulation rate is less than 20% B: Coagulation degree is 20% or more and less than 25% C: Coagulation degree is 25% or more and less than 30% D: Coagulation degree is 30% or more and less than 35% E: Cohesion rate is 35% or more

[0163] [Fixation] A color laser printer (HP Color LaserJet 3525dn, manufactured by Hewlett-Packard Co.) with the fixing unit removed was prepared, the toner was removed from the cyan cartridge, and the toner to be evaluated was replaced with the cyan cartridge. Next, the image receiving paper (Canon Office Planner 64 g / m 2 ) was used to create an unfixed toner image (0.9 mg / cm2) measuring 2.0 cm in length and 15.0 cm in width. 2 ) was formed at a position 1.0 cm from the upper end in the paper feed direction. Next, the removed fixing unit was modified so that the fixing temperature and process speed could be adjusted, and a fixing test of an unfixed image was carried out using this. First, in a normal temperature and humidity environment (23°C, 60% RH), the process speed was set to 230 mm / s and the fixing linear pressure was set to 27.4 kgf. The initial temperature was 85°C and the set temperature was increased in increments of 5°C, and the unfixed image was fixed at each temperature. The evaluation criteria for low-temperature fixability are as follows: The low-temperature fixation start point is when the surface of the image is heated to 4.9 kPa (50 g / cm 2 This is the minimum temperature at which the number of peeled images of 150 μm or more in diameter is less than 3 when the image is rubbed 5 times at a speed of 0.2 m / s with a load of 1000 g / cm2 (Silbon paper (Dasper K-3)). If the fixing is not performed properly, the number of peeled images tends to increase. is located. The evaluation criteria are as follows. A: The low temperature side fixing start point is 115℃ or less B: The low temperature side fixing start point is 1 20 ℃ or higher but less than 130℃ C: The low temperature side fixing start point is 130℃ or higher and less than 145℃ D: The low-temperature side fixing start point is 145°C or higher and less than 160°C. E: The low temperature side fixing start point is 160℃ or higher

[0164] [Evaluation of toner charging stability] The developing device with the cartridge inserted was left in a high temperature and high humidity environment (temperature 30°C, humidity 80% RH) for 24 hours, and then the process speed was set to 200 mm / s in cyan monochrome mode. 5,000 copies of the "E" character (image printing rate 1%) were printed out in intermittent printing mode (2-second pause after every two copies). The fog density on the drum was measured using the following method immediately after printing the first copy (initial stage) and the day after printing the 5,000th copy (after 5k). A solid white image is printed out, the cartridge is removed at the time of transfer, a colorless transparent tape is attached to the drum before transfer, and the tape is then attached to a piece of paper (the same type as the transfer paper). The density D1 of the part of the tape attached to the paper is measured using a "white light photometer TC-6DS" (manufactured by Tokyo Denshoku Co., Ltd.). On the other hand, the tape that was not attached to the drum was directly attached to a piece of paper, and the density D0 was measured under the same conditions. The density difference (D1-D0) was taken as the fog density, and the increase rate of the fog density between the initial stage and after 5k was evaluated. An amber filter was used. The increase rate (%) of fog density is calculated by the following formula. Increase rate of fog density (%) = (Fog density after 5k - Initial fog density) / Initial fog density It is known that when a toner having poor durability (charge stability) is evaluated by this evaluation method, the fog value on the drum increases. The evaluation criteria are as follows. A: The increase rate (%) of fog density is less than 1.0 B: Increase rate (%) of fog density is 1.0 or more and less than 2.0 C: Increase rate (%) of fog density is 2.0 or more and less than 3.0 D: Increase rate (%) of fog density is 3.0 or more and less than 4.0 E: Increase in fog density (%) is 4.0 or more

[0165] [Toner cracking and chipping (evaluation of brittleness)] The following evaluation was carried out to evaluate the durability of the toner against cracking and chipping. That is, the same durability test as above was carried out in a low temperature and low humidity environment (temperature 15°C, humidity 10% RH) with a printing rate of 0.0%, and a solid image was output for every 1000 sheets. Next, the number of sheets with streaked images due to development failure caused by cracked toner or chipped toner was evaluated according to the following criteria. Here, a streaky image due to poor development is judged by observing the toner and developing blade in the cartridge at the time when the streaks on the image occur. This corresponds to the case where it is confirmed that there is broken or chipped toner in the cartridge, and furthermore, that such toner is fused to the developing blade. The toner and developing blade are observed using a scanning electron microscope (SEM). The specimen was observed at a magnification of 1000x using a microscope. The evaluation criteria are as follows. A: The number of occurrences is 20,000 or more. B: The number of occurrences is between 15,000 and 20,000 C: The number of occurrences is between 10,000 and 15,000 D: Number of occurrences is between 5,000 and 10,000 E: Number of occurrences is less than 5,000

[0166] [Table 4]

Claims

1. A toner comprising toner particles, The toner particles contain a binder resin, a resin A and a resin B, The resin A has a substituted or unsubstituted silyl group in the molecule and has a structure represented by the following formula (1): (In the formula (1), P 1 represents a polyester resin portion, L 1 represents a single bond or a divalent linking group; R 1 ~R 3 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 or more carbon atoms, an alkoxy group having 1 or more carbon atoms, an aryl group having 6 or more carbon atoms, or a hydroxy group; at least one of R 1 to R 3 represents an alkoxy group having 1 or more carbon atoms or a hydroxy group; m represents a positive integer; 1 , multiple R 1 , multiple R 2 and multiple R 3 may be the same or different.) the substituent of the substituted silyl group is at least one selected from the group consisting of an alkyl group having one or more carbon atoms, an alkoxy group having one or more carbon atoms, a hydroxy group, a halogen atom, and an aryl group having six or more carbon atoms; The toner is characterized in that the resin B has an azo group in the molecule.

2. 2. The toner according to claim 1, wherein the content of silicon atoms in the resin A is 0.02% by mass to 10.00% by mass.

3. The R 1 ~R 3 The toner according to claim 1 , wherein each independently represents an alkoxy group or a hydroxy group having one or more carbon atoms.

4. Said L 1 The toner according to any one of claims 1 to 3, wherein is represented by the following formula (2): (R in formula (2) 5 represents a single bond, an alkylene group, or an arylene group. 1 represents a bonding site to the silicon atom in formula (1).

5. 5. The toner according to claim 1, wherein the resin A has a weight average molecular weight of 3,000 to 100,000.

6. The toner according to any one of claims 1 to 5, wherein the resin B contains a structure represented by the following formula (11A): Ar 11 -N=N-Ar 21 ・・・(11A) (In formula (11), Ar 11 , Ar 21 Each independently represents a substituted or unsubstituted aromatic group. 11 , Ar 21 At least one of the groups has a substituent, and the substituent serves as a "linking group" to form a bonding site with the organic resin in the resin B.

7. The toner according to any one of claims 1 to 6, wherein the resin B contains a structure represented by the following formula (12A): (In formula (12A), R 51 , R 61 each independently represents a substituted or unsubstituted alkyl group, a substituted or unsubstituted phenyl group, OR 7 group, or NR 8 R 9 R represents a group. 7 ~R 9 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted phenyl group, or an aralkyl group. 31 represents a substituted or unsubstituted aryl group. 51 , R 61 , Ar 31 At least one of the groups has a substituent, and the substituent serves as a "linking group" to form a bonding site with the organic resin in resin B.)

8. 8. The toner according to claim 1, wherein the weight average molecular weight of the resin B is 3,000 to 100,000.

9. When the glass transition temperature Tg of the resin A is Tg(A), the glass transition temperature Tg of the resin B is Tg(B), and the glass transition temperature Tg of the binder resin is Tg(C), 9. The toner according to claim 1, which satisfies the following relational expressions (i) and (ii): Tg(A)>Tg(C)...(i) Tg(B)>Tg(C)...(ii)

10. the binder resin is a copolymer of styrene and a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 8 carbon atoms, The toner according to any one of claims 1 to 9, wherein the copolymerization ratio (styrene:(meth)acrylic acid alkyl ester (mass ratio)) is from 55:45 to 80:20.

Citation Information

Patent Citations

  • Electrophotographic toner

    JP1995239573A

  • Toner and its production

    JP2000122341A

  • Electrostatic charge image developing toner

    JP2006259359A

  • Toner for electrophotography, developer for electrophotography, toner cartridge, process cartridge, and image forming apparatus

    JP2012189692A

  • toner

    JP2015043049A